Electrolyte, method for producing electrolyte, battery, method for producing battery, and vehicle
Patent Information
- Application Number
- CN202580023402.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-22
- Filing Date
- 2025-03-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]然而,专利文献1~3存在电池的热稳定性不足,电池的自放电大的问题
[0090]根据本发明,可以提供能够同时实现电池的热稳定性的提高和电池的自放电的抑制的非水电解液。而且,可以提供具备该非水电解液的非水电解液电池。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to electrolytes, methods for manufacturing electrolytes, batteries, methods for manufacturing batteries, and vehicles. Background Technology
[0002] Non-aqueous electrolyte batteries, such as lithium-ion batteries, are finding practical applications in a wide range of uses, from consumer power sources like mobile phones and laptops to automotive power supplies. However, in recent years, the demand for high-performance non-aqueous electrolyte batteries has been increasing, particularly regarding improvements in various battery characteristics such as high capacity, low-temperature performance, high-temperature storage, cycle life, and safety during overcharging.
[0003] To date, a great deal of technology has been studied for various battery components, including the active materials of the positive and negative electrodes and the non-aqueous electrolyte, as means to improve the input and output characteristics of non-aqueous electrolyte secondary batteries.
[0004] Patent document 1 describes that by introducing at least one of the following into a container containing a specific formula (1): M(FSO3) x By further adding LiPF6 to the non-aqueous electrolyte of the fluorosulfonate, and setting the ratio of the fluorosulfonate to LiPF6 to a specific range, a non-aqueous electrolyte secondary battery with improved initial charge capacity and output / input characteristics can be obtained.
[0005] Patent document 2 describes a solution containing one or more compounds selected from group (A) and a fluorosulfonate (B) having a specific structure. The content of the compound belonging to group (A) in the non-aqueous electrolyte is set within a specific range, and the mass ratio of the specific fluorosulfonate to the content is set to 1 or less. This improves the input-output characteristics. Group (A) consists of a compound represented by a specific formula (1): X-SO2-Y-SO2-Z and a cyclic compound having an SO3 structure.
[0006] Patent document 3 describes that a lithium bis(fluorosulfonyl)imide composition containing more than 90% by mass of lithium bis(fluorosulfonyl)imide and a specific amount of LiFSO3 can improve discharge characteristics at high temperature, input and output characteristics at low temperature, and rate performance at room temperature.
[0007] However, patent documents 1-3 have problems such as insufficient thermal stability of the battery and large self-discharge of the battery.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: International Publication No. 2011 / 099585
[0011] Patent Document 2: Japanese Patent Application Publication No. 2023-130374
[0012] Patent Document 3: Japanese Patent Application Publication No. 2018-35059 Summary of the Invention
[0013] The problem that the invention aims to solve
[0014] The purpose of this invention is to solve the above-mentioned problems and provide a non-aqueous electrolyte that can simultaneously improve the thermal stability of the battery and suppress its self-discharge.
[0015] Problem Solving Methods
[0016] In view of the above-mentioned actual situation, the inventors conducted in-depth research and found that when a non-aqueous electrolyte contains hexafluorophosphate, bis(fluorosulfonyl)imide salt and a compound containing a specific sulfonic acid anion in a specific ratio, a non-aqueous electrolyte battery with improved thermal stability and suppressed self-discharge can be obtained, thus completing the present invention.
[0017] That is, the main point of this invention is as follows.
[0018] [1] An electrolyte comprising a bis(fluorosulfonyl)imide salt, a hexafluorophosphate, a compound containing an anion represented by the following general formula (1), and a non-aqueous solvent.
[0019] The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 0.45.
[0020] In the electrolyte, the content of a compound containing an anion represented by the general formula (1) is 0.03% by mass or more in 100% by mass.
[0021] R 1 SO3 - (1)
[0022] R 1 This represents a halogen atom.
[0023] [2] An electrolyte comprising a bis(fluorosulfonyl)imide salt, a hexafluorophosphate, a compound containing an anion represented by the following general formula (2), and a non-aqueous solvent.
[0024] The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 1.
[0025] In the electrolyte, the content of a compound containing an anion represented by the general formula (2) is 0.01% by mass or more in 100% by mass.
[0026] R 2 SO3 - (2)
[0027] R 2 It represents an alkyl group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom.
[0028] [3] According to the electrolyte described in [1] or [2], wherein,
[0029] The concentration of the bis(fluorosulfonyl)imide salt in the electrolyte is 8% by mass or more.
[0030] [4] The electrolyte according to any one of [1] to [3], wherein,
[0031] The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is 0.01 or more.
[0032] [5] The electrolyte according to any one of [1] to [4], wherein,
[0033] The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 0.2.
[0034] [6] The electrolyte according to any one of [1] to [5], wherein,
[0035] The mass ratio of the compound containing the anion represented by the general formula (1) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 3.7 or less.
[0036] [7] The electrolyte according to any one of [1] to [6], wherein,
[0037] The mass ratio of the compound containing the anion represented by the general formula (1) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 0.0001 or more.
[0038] [8] The electrolyte according to any one of [1] to [7], wherein,
[0039] The bis(fluorosulfonyl)imide salt is LiN(FSO2)2.
[0040] The hexafluorophosphate is LiPF6.
[0041] Compounds containing the anion represented by the general formula (1) are compounds represented by the following general formula (1-1).
[0042] LiR 1SO3 (1-1)
[0043] R 1 This represents a halogen atom.
[0044] [9] The electrolyte according to any one of [1] to [8], wherein,
[0045] The electrolyte further comprises at least one compound (A) selected from the following: cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, cyclic compounds having ether bonds, non-fluorinated carboxylic esters, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, boron-containing anionic compounds, compounds containing oxalate complex anions, and compounds containing phosphate anions having P=O and PF bonds, wherein the bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and compounds containing anions represented by the general formula (1) are excluded.
[0046]
[10] According to the electrolyte described in [9], wherein,
[0047] The compound (A) comprises at least one compound selected from the compounds containing oxalate complex anions, compounds containing phosphate anions having P=O and PF bonds, cyclic carbonates having carbon-carbon unsaturated bonds, and fluorinated cyclic carbonates.
[0048]
[11] The electrolyte according to any one of [2] to [5], wherein,
[0049] The mass ratio of the compound containing the anion represented by the general formula (2) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 3.7 or less.
[0050]
[12] The electrolyte according to any one of [2]~[5],
[11] , wherein,
[0051] The mass ratio of the compound containing the anion represented by the general formula (2) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 0.0001 or more.
[0052]
[13] The electrolyte according to any one of [2]~[5],
[11] ,
[12] , wherein,
[0053] The bis(fluorosulfonyl)imide salt is LiN(FSO2)2.
[0054] The hexafluorophosphate is LiPF6.
[0055] Compounds containing the anion represented by the general formula (2) are compounds represented by the following general formula (2-1).
[0056] LiR 2 SO3 (2-1)
[0057] R 2 It represents an alkyl group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom.
[0058]
[14] The electrolyte according to any one of [2]~[5],
[11] ,
[12] , and
[13] , wherein,
[0059] The electrolyte further comprises at least one compound (A) selected from the following: cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, cyclic compounds having ether bonds, non-fluorinated carboxylic esters, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, boron-containing anionic compounds, compounds containing oxalate complex anions, and compounds containing phosphate anions having P=O and PF bonds, wherein the bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and compounds containing anions represented by the general formula (2) are excluded.
[0060]
[15] According to the electrolyte described in
[14] , wherein,
[0061] The compound (A) comprises at least one compound selected from the compounds containing oxalate complex anions, compounds containing phosphate anions having P=O and PF bonds, cyclic carbonates having carbon-carbon unsaturated bonds, and fluorinated cyclic carbonates.
[0062]
[16] A method for manufacturing an electrolyte, the method comprising:
[0063] The process of dissolving bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and a compound containing an anion represented by the following general formula (1) in a non-aqueous solvent,
[0064] The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 0.45.
[0065] In 100% by mass of the electrolyte, the content of the compound containing the anion represented by the general formula (1) is 0.03% by mass or more.
[0066] R 1SO3 - (1)
[0067] R 1 This represents a halogen atom.
[0068]
[17] A method for manufacturing an electrolyte, the method comprising:
[0069] The process of dissolving bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and a compound containing anion represented by the following general formula (2) in a non-aqueous solvent,
[0070] The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 1.
[0071] In 100% by mass of the electrolyte, the content of the compound containing the anion represented by the general formula (2) is 0.01% by mass or more.
[0072] R 2 SO3 - (2)
[0073] R 2 It represents an alkyl group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom.
[0074]
[18] A battery comprising a positive electrode, a negative electrode and an electrolyte as described in any one of [1] to
[15] .
[0075]
[19] According to the battery described in
[18] , wherein,
[0076] The positive electrode comprises a compound represented by the following formula (3).
[0077] Li 1+x MO2 (3)
[0078] In the composition formula (3), x satisfies -0.1≤x≤0.5, and M contains an element containing at least one transition metal.
[0079]
[20] According to the battery described in
[19] , wherein,
[0080] The Ni content in M is above 55 mol%.
[0081]
[21] According to the battery described in
[18] , wherein,
[0082] The positive electrode comprises a compound represented by the following formula (4).
[0083] LiMn 1-y Fe y PO4 (4)
[0084] In equation (4), y satisfies 0 <y≤1。
[0085]
[22] A method for manufacturing a battery, the method comprising:
[0086] The process of housing the positive and negative electrodes in the outer casing, and
[0087] The process of injecting the electrolyte as described in any one of [1] to
[15] into the outer casing.
[0088]
[23] A vehicle comprising any one of the batteries described in
[18] to
[21] .
[0089] The effects of the invention
[0090] According to the present invention, a non-aqueous electrolyte capable of simultaneously improving the thermal stability of the battery and suppressing its self-discharge can be provided. Furthermore, a non-aqueous electrolyte battery incorporating this non-aqueous electrolyte can be provided.
[0091] The inventors speculate the following reasons for the superior effects of the non-aqueous electrolyte with the structure of the present invention. Hexafluorophosphate anion is unstable at high temperatures, thus making the battery prone to decomposition and heat generation when at high temperatures, but it has the effect of protecting the aluminum current collector from dissolution. On the other hand, bis(fluorosulfonyl)imide anion is a compound with high thermal stability, but it will dissolve due to the instability of the film formed on the electrode, thus it is speculated that it will cause self-discharge of the battery.
[0092] This invention discovers that by constructing a non-aqueous electrolyte in which bis(fluorosulfonyl)imide salt is mixed with hexafluorophosphate at a specific ratio or higher, and further contains a compound containing specific sulfonic acid anions, it is possible to simultaneously improve the battery's thermal stability (suppressing heat generation under high-temperature conditions) and suppress self-discharge. The reason is presumably that increasing the ratio of bis(fluorosulfonyl)imide anions improves thermal stability, the specific sulfonic acid anions stabilize the coating on the electrode surface, and the three anions react with aluminum in a good balance, thereby forming a coating with low solubility on the electrode surface. As a result, it is presumably possible to improve the battery's thermal stability and suppress its self-discharge. Detailed Implementation
[0093] The following describes in detail the methods for implementing the present invention. However, the description below is merely one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents. Furthermore, the present invention can be implemented in any way without departing from its spirit.
[0094] [1. First Electrolyte]
[0095] [1-1. Hexafluorophosphates, bis(fluorosulfonyl)imide salts, and compounds containing anions represented by general formula (1)]
[0096] In one embodiment of the present invention, the non-aqueous electrolyte (hereinafter sometimes referred to as "first electrolyte") contains hexafluorophosphate, bis(fluorosulfonyl)imide salt and a compound containing anion represented by the following general formula (1), wherein the mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is 0.45 or less, and the content of the compound containing anion represented by general formula (1) is 0.03% by mass or more in 100% by mass of the electrolyte.
[0097] R 1 SO3 - (1)
[0098] (R 1 (This represents a halogen atom.)
[0099] The following is an explanation of each component.
[0100] Hexafluorophosphate is a salt formed by the hexafluorophosphate anion and the counter cation.
[0101] Bis(fluorosulfonyl)imide salts are salts formed by the bis(fluorosulfonyl)imide anion and the counter cation.
[0102] The cations constituting hexafluorophosphate and bis(fluorosulfonyl)imide salt are preferably alkali metal cations such as lithium, sodium, and potassium, and more preferably lithium cations.
[0103] In the above general formula (1), R 1 This represents a halogen atom.
[0104] The halogen atom mentioned above is preferably a fluorine atom.
[0105] In general formula (1), in R 1 In the case of fluorine atoms, there is a tendency to further and more effectively suppress self-discharge and heat generation within the battery.
[0106] Compounds containing anions represented by general formula (1) are usually acids (e.g., those represented by R). 1 An acid (represented by SO3H) or a salt (a salt formed by an anion represented by general formula (1) and a counter cation), preferably a salt. As a counter cation, an alkali metal cation such as lithium, sodium, or potassium is preferred, and lithium cation is more preferred.
[0107] The concentration of hexafluorophosphate in the non-aqueous electrolyte is typically 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and most preferably 2% by mass or more. It is also typically 18% by mass or less, preferably 16% by mass or less, more preferably 14% by mass or less, further preferably 11% by mass or less, even more preferably 9% by mass or less, still more preferably 7% by mass or less, particularly preferably 6% by mass or less, and most preferably 5% by mass or less. When the concentration of hexafluorophosphate in the non-aqueous electrolyte is within the above range, it tends to suppress battery self-discharge.
[0108] Relative to the total amount of non-aqueous electrolyte, the concentration of bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is typically 3.5% by mass or more, preferably 5% by mass or more, more preferably 7% by mass or more, further preferably 8% by mass or more, particularly preferably 9% by mass or more, and most preferably 10% by mass or more. Additionally, it is typically 25% by mass or less, preferably 22% by mass or less, more preferably 20% by mass or less, particularly preferably 17% by mass or less, and most preferably 15% by mass or less. When the concentration of bis(fluorosulfonyl)imide salt is within the above-mentioned range, there is a tendency for improved thermal stability of the battery.
[0109] Relative to the total amount of the non-aqueous electrolyte, the concentration of the compound containing the anion represented by general formula (1) in the non-aqueous electrolyte is 0.03% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.2% by mass or more, and most preferably 0.5% by mass or more. It is generally 10% by mass or less, preferably 5% by mass or less, more preferably 4% by mass or less, particularly preferably 3% by mass or less, and most preferably 2.5% by mass or less. When the concentration of the compound containing the anion represented by general formula (1) in the non-aqueous electrolyte is within the above-mentioned range, it tends to suppress battery self-discharge and heat generation.
[0110] The mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is 0.45 or less, preferably 0.40 or less, more preferably 0.35 or less, even more preferably 0.30 or less, particularly preferably 0.25 or less, and most preferably 0.2 or less. Additionally, it is typically 0.01 or more, preferably 0.04 or more, more preferably 0.06 or more, particularly preferably 0.1 or more, and most preferably 0.13 or more. When the mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is within the above range, it tends to suppress battery self-discharge and heat generation.
[0111] The mass ratio of the compound containing the anion represented by general formula (1) in the non-aqueous electrolyte to the mass of the bis(fluorosulfonyl)imide salt is not particularly limited, but is generally 3.7 or less, preferably 2.6 or less, more preferably 1.6 or less, further preferably 0.8 or less, particularly preferably 0.4 or less, and most preferably 0.3 or less. Additionally, it is generally 0.0001 or more, preferably 0.0005 or more, more preferably 0.001 or more, particularly preferably 0.002 or more, and most preferably 0.003 or more. When the mass ratio of the compound containing the anion represented by general formula (1) in the non-aqueous electrolyte to the mass of the bis(fluorosulfonyl)imide salt is within the above range, it tends to suppress self-discharge and heat generation within the battery.
[0112] The identification and content determination of the above-mentioned compounds in the non-aqueous electrolyte were performed using ion chromatography and nuclear magnetic resonance (NMR) spectrophotometry.
[0113] In the first electrolyte, the bis(fluorosulfonyl)imide salt is preferably LiN(FSO2)2, the hexafluorophosphate is preferably LiPF6, and the compound containing the anion represented by general formula (1) is preferably the compound represented by the following general formula (1-1).
[0114] LiR 1 SO3 (1-1)
[0115] (R in general formula (1-1) 1 R in general formula (1) 1 (The methods for optimization are the same.)
[0116] The masses of LiN(FSO2)2, LiPF6, and compounds represented by general formula (1-1) in the first electrolyte, and their mass ratios, are preferably within the ranges described above, as well as the masses of bis(fluorosulfonyl)imide salt, hexafluorophosphate, and compounds containing anions represented by general formula (1).
[0117] [1-2. Other electrolytes]
[0118] Lithium salts
[0119] Lithium salts are generally used as electrolytes in non-aqueous electrolytes, excluding bis(fluorosulfonyl)imide salts, hexafluorophosphates, and compounds containing anions represented by general formula (1). No particular restriction is placed on the use of any lithium salt known to be suitable for this application; specifically, the following lithium salts are examples.
[0120] Examples include: lithium fluoroborate, lithium fluorophosphate, lithium tungstate, lithium carboxylate, lithium imide, lithium methylate, lithium oxalate, and fluorine-containing organic lithium salts.
[0121] From the perspective of improving low-temperature output characteristics, high-rate charge-discharge characteristics, impedance characteristics, high-temperature storage characteristics, and cycle characteristics, LiBF4 is more preferred as a lithium fluoroborate salt; Li2PO3F and LiPO2F2 are more preferred as lithium fluorophosphate salts; LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, and lithium cyclic 1,3-perfluoropropane disulfonylimide are more preferred as lithium methyl salts; LiC(FSO2)3, LiC(CF3SO2)3, and LiC(C2F5SO2)3 are more preferred as lithium methyl salts; and lithium difluorooxalate, lithium difluorooxalate borate, lithium bis(oxalate)borate, lithium tetrafluorooxalate phosphate, lithium difluorobis(oxalate)phosphate, and lithium tri(oxalate)phosphate are more preferred as lithium oxalate. The above electrolyte salts can be used alone or in combination of two or more.
[0122] The total content of electrolytes in the non-aqueous electrolyte (the total content of bis(fluorosulfonyl)imide salt, hexafluorophosphate, compounds containing anions represented by general formula (1), and other electrolytes) is not particularly limited, but is generally 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, and generally 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less, relative to the total amount of the non-aqueous electrolyte. When the electrolyte content is within the above range, the conductivity can be adapted to battery operation, and therefore there is a tendency to obtain sufficient output characteristics.
[0123] [1-3. Non-aqueous solvents]
[0124] The first electrolyte is similar to that of a typical non-aqueous electrolyte, usually containing a non-aqueous solvent in which the electrolyte described above is dissolved as its main component. The non-aqueous solvent used need only be sufficient to dissolve the electrolyte; there are no particular restrictions, and known organic solvents can be used. Examples of organic solvents include saturated cyclic carbonates, chain carbonates, chain carboxylic esters, cyclic carboxylic esters, ether compounds, and sulfone compounds, but these are not specifically limited to these. One organic solvent can be used alone, or two or more can be used in combination.
[0125] The combination of two or more organic solvents is not particularly limited, and examples include: saturated cyclic carbonates and chain carbonates, saturated cyclic carbonates and chain carboxylic esters, cyclic carboxylic esters or chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylic esters. Among these, saturated cyclic carbonates and chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylic esters are preferred.
[0126] [1-3-1. Saturated cyclic carbonates]
[0127] Saturated cyclic carbonates, for example, include saturated cyclic carbonates having 2 to 4 carbon atoms. From the viewpoint of improving battery characteristics due to increased lithium-ion dissociation, saturated cyclic carbonates having 2 to 3 carbon atoms are preferred.
[0128] Examples of saturated cyclic carbonates include ethylene carbonate, propylene carbonate, and butyl carbonate. Ethyl carbonate or propylene carbonate is preferred, and ethylene carbonate, which is less prone to oxidation / reduction, is even more preferred. A single saturated cyclic carbonate can be used alone, or two or more can be used in any combination and ratio.
[0129] The content of saturated cyclic carbonate is not particularly limited, and can be arbitrary as long as it does not significantly impair the effect of the invention of this embodiment. Relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte, it is typically 3% by volume or more, preferably 5% by volume or more, and on the other hand, typically 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. By setting the content of saturated cyclic carbonate within this range, the following advantages are achieved: a decrease in conductivity due to a decrease in the dielectric constant of the non-aqueous electrolyte is avoided; it is easier to set the high-current discharge characteristics and cycle characteristics of the non-aqueous electrolyte secondary battery within a favorable range; the oxidation / reduction resistance of the non-aqueous electrolyte is improved; and the stability of the negative electrode and the stability during high-temperature storage are improved.
[0130] It should be noted that the volume % in this embodiment refers to the volume at 25°C and 1 atmosphere.
[0131] [1-3-2. Chain carbonates]
[0132] As a chain carbonate, for example, a chain carbonate with 3 to 7 carbon atoms can be used. In order to adjust the viscosity of the electrolyte to an appropriate range, a chain carbonate with 3 to 5 carbon atoms is preferred.
[0133] Examples of chain carbonates include: dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, methyl ethyl carbonate, and methyl n-propyl carbonate. Dimethyl carbonate, diethyl carbonate, or methyl ethyl carbonate are particularly preferred.
[0134] Alternatively, fluorocarbonate chains (hereinafter sometimes simply referred to as "fluorocarbonate chains") containing fluorine atoms may also be used. The number of fluorine atoms in a fluorocarbonate chain is not particularly limited, but is typically six or less, preferably four or less. In the case of a fluorocarbonate chain having multiple fluorine atoms, these multiple fluorine atoms may be bonded to the same carbon atom or to different carbon atoms.
[0135] Examples of fluorinated chain carbonates include: fluoromethyl methyl carbonate and other fluorodimethyl carbonate derivatives; fluoroethyl carbonate and other fluoromethyl carbonate derivatives; fluoroethyl (2-fluoroethyl) carbonate and other fluorodiethyl carbonate derivatives; and so on.
[0136] Chain carbonates can be used alone or in combination of two or more in any ratio.
[0137] The content of the chain carbonate is not particularly limited, but relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte, it is typically 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, and typically 90% by volume or less, preferably 85% by volume or less, more preferably 80% by volume or less. By setting the content of the chain carbonate within the above range, the viscosity of the non-aqueous electrolyte can be set within an appropriate range, the decrease in ionic conductivity can be suppressed, and thus it is easier to set the output characteristics of the non-aqueous electrolyte secondary battery within a favorable range.
[0138] Furthermore, by combining ethylene carbonate in specific amounts relative to specific chain carbonates, battery performance can be significantly improved.
[0139] For example, when dimethyl carbonate and ethyl methyl carbonate are selected as specific chain carbonates, the content of ethylene carbonate is not particularly limited, and can be arbitrary as long as it does not significantly impair the effect of the invention of this embodiment. The content is typically 15% by volume or more, preferably 20% by volume or more, and typically 45% by volume or less, preferably 40% by volume or less, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte. The content of dimethyl carbonate is typically 20% by volume or more, preferably 30% by volume or more, and typically 50% by volume or less, preferably 45% by volume or less, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte. The content of ethyl methyl carbonate is typically 20% by volume or more, preferably 30% by volume or more, and typically 50% by volume or less, preferably 45% by volume or less, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte. By setting the content within the above ranges, excellent high-temperature stability is achieved, and there is a tendency to suppress gas generation.
[0140] [1-3-3. Chain carboxylic acid esters]
[0141] Examples of chain-like carboxylic acid esters include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, methyl valerate, methyl isobutyrate, ethyl isobutyrate, and methyl pivalate. From the viewpoint of improving battery performance, methyl acetate, ethyl acetate, propyl acetate, or butyl acetate are preferred. Chain-like carboxylic acid esters obtained by replacing some of the hydrogen atoms in the above compounds with fluorine (e.g., methyl trifluoroacetate, ethyl trifluoroacetate, etc.) may also be suitably used.
[0142] The content of chain carboxylic acid esters is typically 1% by volume or more, preferably 5% by volume or more, and more preferably 15% by volume or more, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte. Within this range, the conductivity of the non-aqueous electrolyte can be improved, making it easier to enhance the high-current discharge characteristics of the non-aqueous electrolyte battery. Furthermore, the content of chain carboxylic acid esters is typically 70% by volume or less, preferably 50% by volume or less, and more preferably 40% by volume or less. By setting such an upper limit, the viscosity of the non-aqueous electrolyte can be set within an appropriate range, avoiding a decrease in conductivity, suppressing an increase in negative electrode resistance, and easily setting the high-current discharge characteristics of the non-aqueous electrolyte secondary battery within a favorable range.
[0143] [1-3-4. Cyclic carboxylic esters]
[0144] Examples of cyclic carboxylic acid esters include γ-butyrolactone and γ-valerolactone. γ-Butyrolactone is more preferred. Cyclic carboxylic acid esters obtained by replacing some of the hydrogen atoms in the above compounds with fluorine may also be used suitably.
[0145] The content of cyclic carboxylic acid esters is typically 1% by volume or more, preferably 5% by volume or more, and more preferably 15% by volume or more, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte. Within this range, the conductivity of the non-aqueous electrolyte can be improved, making it easier to enhance the high-current discharge characteristics of the non-aqueous electrolyte secondary battery. Furthermore, the content of cyclic carboxylic acid esters is typically 70% by volume or less, preferably 50% by volume or less, and more preferably 40% by volume or less. By setting such an upper limit, it is easy to set the viscosity of the non-aqueous electrolyte within an appropriate range, avoiding a decrease in conductivity, suppressing an increase in negative electrode resistance, and easily setting the high-current discharge characteristics of the non-aqueous electrolyte secondary battery within a favorable range.
[0146] [1-3-5. Ether compounds]
[0147] As ether compounds, preferred are chain ethers with 3 to 10 carbon atoms, such as dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether; and cyclic ethers with 3 to 6 carbon atoms, such as tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxane, 2-methyl-1,3-dioxane, 4-methyl-1,3-dioxane, and 1,4-dioxane. It should be noted that fluorine can replace some of the hydrogen atoms in the above ether compounds.
[0148] Among them, as a chain ether with 3 to 10 carbon atoms, from the viewpoint of high solvation ability for lithium ions, improved ion dissociation, low viscosity, and high ionic conductivity, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane are preferred. As a cyclic ether with 3 to 6 carbon atoms, from the viewpoint of high ionic conductivity, tetrahydrofuran, 1,3-dioxane, and 1,4-dioxane are preferred.
[0149] The content of ether compounds is not particularly limited, and can be arbitrary as long as it does not significantly impair the effect of the invention of this embodiment. Relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte, it is typically 1% by volume or more, preferably 2% by volume or more, more preferably 3% by volume or more, and typically 30% by volume or less, preferably 25% by volume or less, more preferably 20% by volume or less. When the content of ether compounds is within the above range, it is easy to ensure the effects of increased lithium-ion dissociation due to the ether compounds and increased ionic conductivity due to decreased viscosity of the non-aqueous electrolyte. Furthermore, when the negative electrode active material is a carbonaceous material, the phenomenon of co-intercalation between chain ethers and lithium ions can be suppressed, thus allowing the input / output characteristics and charge / discharge rate characteristics to be set within a suitable range.
[0150] [1-3-6. Sulfone compounds]
[0151] As a sulfone compound, there are no particular limitations; it can be a cyclic sulfone or a chain sulfone. In the case of a cyclic sulfone, the number of carbon atoms is usually 3 to 6, preferably 3 to 5; in the case of a chain sulfone, the number of carbon atoms is usually 2 to 6, preferably 2 to 5. Furthermore, there are no particular limitations on the number of sulfonyl groups in one molecule of the sulfone compound; it is usually one or two.
[0152] Examples of cyclic sulfones include: trimethylene sulfones, tetramethylene sulfones, and hexamethylene sulfones as monosulfone compounds; and trimethylene disulfones, tetramethylene disulfones, and hexamethylene disulfones as disulfone compounds. From the viewpoint of dielectric constant and viscosity, tetramethylene sulfones, tetramethylene disulfones, and hexamethylene sulfones are more preferred, and tetramethylene sulfones (sulfolane) are particularly preferred.
[0153] As sulfolane compounds, sulfolane and sulfolane derivatives are preferred. As sulfolane derivatives, compounds obtained by replacing one or more hydrogen atoms bonded to the carbon atoms constituting the sulfolane ring with fluorine atoms, alkyl groups, or fluorine-substituted alkyl groups are preferred.
[0154] From the perspective of high ionic conductivity and high input-output ratio, 2-methylcyclobutanesulfone, 3-methylcyclobutanesulfone, 2-fluorocyclobutanesulfone, 3-fluorocyclobutanesulfone, 2,3-difluorocyclobutanesulfone, 2-trifluoromethylcyclobutanesulfone, or 3-trifluoromethylcyclobutanesulfone are preferred.
[0155] In addition, examples of chain sulfones include: dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, monofluoromethyl methyl sulfone, difluoromethyl sulfone, trifluoromethyl methyl sulfone, pentafluoroethyl methyl sulfone, etc. Among these, from the viewpoint of improving the high-temperature storage stability of the electrolyte, dimethyl sulfone, ethyl methyl sulfone, or monofluoromethyl methyl sulfone are preferred.
[0156] The content of sulfone compounds is not particularly limited, and can be arbitrary as long as it does not significantly impair the effect of the invention of this embodiment. Relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte, it is typically 0.3% by volume or more, preferably 0.5% by volume or more, more preferably 1% by volume or more, and typically 40% by volume or less, preferably 35% by volume or less, more preferably 30% by volume or less. When the content of sulfone compounds is within the above range, there is a tendency to obtain an electrolyte with excellent high-temperature storage stability.
[0157] [1-4. Additives]
[0158] The first electrolyte may contain various additives without significantly impairing the effects of the present invention. Any conventionally known additives may be used. It should be noted that an additive may be used alone, or two or more may be used in any combination and ratio.
[0159] Examples of additives optionally included in non-aqueous electrolytes include at least one compound (A) selected from the following: cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, non-fluorinated carboxylic esters, cyclic compounds having ether bonds, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, compounds containing borate anions, compounds containing phosphate anions having P=O and PF bonds, and compounds containing oxalate complex anions (excluding bis(fluorosulfonyl)imide salts, hexafluorophosphates, and compounds represented by general formula (1-1)). Specific examples include compounds described in International Publication No. 2015 / 111676.
[0160] Compound (A) is preferably selected from at least one compound selected from cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, cyclic compounds having ether bonds, non-fluorinated carboxylic acid esters, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, boron-containing anionic compounds, compounds containing oxalate complex anions, and compounds containing phosphate anions having P=O bonds and PF bonds (excluding bis(fluorosulfonyl)imide salts, hexafluorophosphates, and compounds containing anions represented by general formula (1)).
[0161] Preferably, the compound is selected from at least one anion-containing compound (hereinafter also referred to as "a compound containing a specific anion") selected from compounds containing phosphate anions having PF bonds and P=O bonds, and compounds containing oxalate complex anions, or at least one carbonate compound (hereinafter also referred to as "a specific carbonate compound") selected from cyclic carbonates having carbon-carbon unsaturated bonds and fluorinated cyclic carbonates. From the viewpoint of suppressing the increase of the battery's internal resistance, it is particularly preferred to select at least one anion-containing compound selected from compounds containing phosphate anions having PF bonds and P=O bonds, and compounds containing oxalate complex anions.
[0162] The content of the additive is not particularly limited, as long as it does not significantly impair the effect of the present invention, and is arbitrary. Relative to the total amount of non-aqueous electrolyte, it is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, and particularly preferably less than 1% by mass.
[0163] Cyclic compounds with ether bonds can be used as auxiliaries in non-aqueous electrolytes, and may also contain substances that can be used as non-aqueous solvents, as shown in "1-3. Non-aqueous solvents". When using cyclic compounds with ether bonds as auxiliaries, they should be used in amounts less than 4% by mass. Compounds containing borate anions, compounds containing oxalate complex anions, compounds containing monofluorophosphate anions, and compounds containing difluorophosphate anions can also be used as auxiliaries in non-aqueous electrolytes, and may also contain substances that can be used as electrolytes, as shown in "1-2. Electrolytes". When using these compounds as auxiliaries, they should be used in amounts less than 8% by mass.
[0164] [1-4-1. Compounds containing specific anions]
[0165] The compounds containing specific anions are typically acids or salts. These compounds are preferably salts, and as counter cations, they are preferably alkali metal cations such as lithium, sodium, or potassium, and more preferably lithium cations.
[0166] At least one anion-containing compound selected from compounds containing phosphate anions with PF bonds and P=O bonds, and compounds containing oxalate complex anions, may be used alone or in combination of two or more in any ratio.
[0167] From the viewpoint of suppressing the amount of gas generated after high-temperature storage, compounds containing phosphate anions with PF bonds and P=O bonds are preferred.
[0168] [1-4-1-1. Compounds containing phosphate anions with PF and P=O bonds]
[0169] Examples of compounds containing phosphate anions with both FP and P=O bonds include: compounds containing PO3F2 - Monofluorophosphate anion, PO2F2 - Compounds containing difluorophosphate anions.
[0170] From the perspective of balancing the battery's output characteristics with electrode interface protection, compounds containing difluorophosphate anions are preferred.
[0171] [1-4-1-2. Compounds containing oxalate complex anions]
[0172] Compounds containing oxalate complex anions are simply compounds whose molecules contain an oxalate complex anion; there are no particular restrictions. Compounds containing oxalate complex anions refer to compounds containing the anion of an acid that forms a complex through coordination or bonding between oxalic acid and a central atom. Examples include compounds containing boron oxalate complex anions (formed by coordination or bonding between oxalic acid and boron atoms) and compounds containing phosphorus oxalate complex anions (formed by coordination or bonding between oxalic acid and phosphorus atoms).
[0173] Examples of borooxaate complex anions include: bis(oxalate)borate anion, difluorooxalate-borate anion, etc. Examples of phosphate oxalate complex anions include: tetrafluorooxalate phosphate anion, difluorobis(oxalate) phosphate anion, tri(oxalate) phosphate anion, etc.
[0174] From the viewpoint of forming a stable composite film on the surface of the electrode, a compound containing borooxate complex anion is preferred, and a compound containing bis(oxate)borate anion is more preferred.
[0175] (Content of compounds containing specific anions)
[0176] When the non-aqueous electrolyte contains a compound containing a specific anion, the content of the compound containing the specific anion in the total amount of the non-aqueous electrolyte (total amount when there are two or more) is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.1% by mass or more, and preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.
[0177] When the content of compounds containing specific anions is within the above-mentioned range, battery characteristics, especially the DCR retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. The reason is not yet clear, but it can be considered that when the content of compounds containing specific anions is within the above-mentioned mass ratio range, the side reactions of non-aqueous electrolyte components on the electrode surface can be suppressed to a minimum.
[0178] The identification and content determination of compounds containing specific anions are performed by nuclear magnetic resonance (NMR) spectrophotometry.
[0179] (The mass ratio of compounds containing a specific anion to compounds containing anion represented by general formula (1))
[0180] The mass ratio of the content of the compound containing the specific anion (total amount when there are two or more) to the content of the compound containing the anion represented by general formula (1) (compound containing the specific anion [g] / compound containing the anion represented by general formula (1) [g]) is generally 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and generally 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. The mass ratio of the content of the compound containing the specific anion to the content of the compound represented by general formula (1-1) (compound containing the specific anion [g] / compound represented by general formula (1-1) [g]) is also preferably within the same range as described above.
[0181] When the mass ratio is within the range described above, the battery characteristics, especially the resistance retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. The reason for this is not yet clear, but it can be considered that by including compounds containing anions represented by general formula (1) and compounds containing specific anions within the range described above mass ratio, the side reactions of the non-aqueous electrolyte components on the electrode surface can be suppressed to a minimum.
[0182] (The mass ratio of compounds containing specific anions to electrolytes)
[0183] When the non-aqueous electrolyte contains a compound containing a specific anion, the mass ratio of the content of the compound containing the specific anion (total amount when there are two or more) to the content of the electrolyte (compound containing the specific anion [g] / electrolyte [g]) is generally 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, even more preferably 0.025 or more, and is generally 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, and even more preferably 0.35 or less.
[0184] When the mass ratios mentioned above are within the aforementioned range, battery characteristics can be significantly improved, especially the resistance retention rate after high-temperature storage, and the amount of gas generated after high-temperature storage can be significantly suppressed. The reason for this is not yet clear, but it can be considered that by including compounds containing specific anions and electrolytes within the aforementioned mass ratio range, the side reactions of the electrolyte in the battery system can be minimized.
[0185] [1-4-2. Specific carbonate compounds]
[0186] The non-aqueous electrolyte preferably comprises at least one carbonate compound selected from cyclic carbonates having carbon-carbon unsaturated bonds and cyclic carbonates having fluorine atoms. Preferably, it comprises a cyclic carbonate having carbon-carbon unsaturated bonds, more preferably, it comprises vinylene carbonate. These can be used alone or in combination of two or more in any ratio. Preferably, unsaturated cyclic carbonates and fluorinated cyclic carbonates are used in combination; more preferably, vinylene carbonate and fluorinated cyclic carbonates are used in combination; and even more preferably, unsaturated cyclic carbonates and monofluoroethylene carbonates are used in combination. A combination of vinylene carbonate and monofluoroethylene carbonate is also preferred.
[0187] (Content of specific carbonate compounds)
[0188] The content of a specific carbonate compound (total of two or more) in the total amount of non-aqueous electrolyte is generally 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more. In addition, it is generally 10% by mass or less, preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.
[0189] When the content of specific carbonate compounds is within the above-mentioned range, battery characteristics, especially durability, can be improved. The reason for this is not yet clear, but it is thought that by including carbonate compounds in this ratio, a film can be formed on the electrode, minimizing the side reactions of non-aqueous electrolyte components.
[0190] The identification and content determination of specific carbonate compounds were performed by nuclear magnetic resonance (NMR) spectrophotometry.
[0191] (The mass ratio of a specific carbonate compound to a compound containing an anion represented by general formula (1))
[0192] The mass ratio of the content of a specific carbonate compound (two or more, total amount) to the content of the compound containing the anion represented by general formula (1) (specific carbonate compound [g] / compound containing the anion represented by general formula (1) [g]) is generally 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and even more preferably 0.5 or more. It is also generally 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. The mass ratio of the content of the specific carbonate compound to the content of the compound represented by general formula (1-1) (specific carbonate compound [g] / compound represented by general formula (1-1) [g]) is also preferably within the same range as described above. When the mass ratio is within the above range, battery characteristics, especially durability, can be improved. The reason for this is not yet clear, but it can be considered that by containing a specific carbonate compound within the above mass ratio range, a film can be formed on the electrode, minimizing the side reactions of the non-aqueous electrolyte components.
[0193] (The specific mass ratio of carbonate compounds to electrolytes)
[0194] In non-aqueous electrolytes, the mass ratio of the content of a specific carbonate compound (total amount when there are two or more) to the content of the electrolyte (specific carbonate compound [g] / electrolyte [g]) is typically 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, further preferably 0.02 or more, and even more preferably 0.025 or more. It is also typically 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, and even more preferably 0.35 or less. When the mass ratio is within the above range, battery characteristics and durability can be improved. The reason for this is not yet clear, but it can be considered that by containing carbonate compounds and electrolytes within the above mass ratio range, a film can be formed on the electrode, minimizing the side reactions of the electrolyte within the battery system.
[0195] [1-4-2-1. Cyclic carbonates with carbon-carbon unsaturated bonds]
[0196] As a cyclic carbonate with carbon-carbon unsaturated bonds (hereinafter also referred to as "unsaturated cyclic carbonate"), it is acceptable as long as it has carbon-carbon double or triple bonds, without any particular limitation. Cyclic carbonates with aromatic rings are also included in unsaturated cyclic carbonates.
[0197] Examples of unsaturated cyclic carbonates include: vinylene carbonates, ethylene carbonates substituted with substituents having aromatic rings, carbon-carbon double bonds, or carbon-carbon triple bonds, phenyl carbonates, vinyl carbonates, allyl carbonates, and catechol carbonates. Among these, vinylene carbonates and ethylene carbonates substituted with substituents having aromatic rings, carbon-carbon double bonds, or carbon-carbon triple bonds are preferred.
[0198] Examples of vinylene carbonates include: vinylene carbonate, methyl vinylene carbonate, 4,5-dimethyl vinylene carbonate, phenyl vinylene carbonate, 4,5-diphenyl vinylene carbonate, vinyl vinylene carbonate, 4,5-vinyl vinylene carbonate, allyl vinylene carbonate, and 4,5-diallyl vinylene carbonate.
[0199] Examples of ethylene carbonates obtained by substitution with substituents having an aromatic ring or carbon-carbon double or triple bonds include: vinyl ethylene carbonate, 4,5-divinyl ethylene carbonate, 4-methyl-5-vinyl ethylene carbonate, 4-allyl-5-vinyl ethylene carbonate, ethynyl ethylene carbonate, 4,5-diethynyl ethylene carbonate, 4-methyl-5-ethynyl ethylene carbonate, 4-vinyl-5-ethynyl ethylene carbonate, 4-allyl-5-ethynyl ethylene carbonate, phenyl ethylene carbonate, 4,5-diphenyl ethylene carbonate, 4-phenyl-5-vinyl ethylene carbonate, 4-allyl-5-phenyl ethylene carbonate, allyl ethylene carbonate, 4,5-diallyl ethylene carbonate, and 4-methyl-5-allyl ethylene carbonate.
[0200] Among them, vinylene carbonate, vinyl ethylene carbonate, and ethynyl ethylene carbonate are preferred because they can form a more stable composite film on the electrode. More preferably, they are selected from one or more of vinylene carbonate and vinyl ethylene carbonate, and even more preferably, they are vinylene carbonate.
[0201] Unsaturated cyclic carbonates can be used alone or in combination of two or more in any ratio.
[0202] [1-4-2-2. Cyclic carbonates with fluorine atoms]
[0203] Cyclic carbonates containing fluorine atoms are only required to have a cyclic carbonate structure and contain fluorine atoms; there are no particular restrictions.
[0204] Examples of cyclic carbonates having fluorine atoms include fluorides and derivatives of cyclic carbonates having 2 or more but less than 6 carbon atoms, such as fluorides of ethylene carbonate (fluoroethylene carbonate) and their derivatives, as well as ethylene carbonate having fluorinated groups. Examples of fluorides of ethylene carbonate include fluorides of ethylene carbonate substituted with alkyl groups (e.g., alkyl groups having 1 or more but less than 4 carbon atoms). Fluoroethylene carbonate and its derivatives having 1 or more but less than 8 fluorine atoms are preferred.
[0205] Examples of fluoroethylene carbonates and their derivatives having 1 or more but less than 8 fluorine atoms, as well as ethylene carbonates containing fluorine groups, include: monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, 4,4-difluoro-5,5-dimethylethylene carbonate, etc.
[0206] From the viewpoint of imparting high ionic conductivity to the electrolyte and easily forming a stable interfacial protective film, it is preferable to select one or more of monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, and 4,5-difluoroethylene carbonate.
[0207] Cyclic carbonates containing fluorine atoms can be used alone or in combination of two or more in any ratio.
[0208] [1-5. Electrolyte manufacturing methods]
[0209] The first electrolyte can be manufactured by dissolving a bis(fluorosulfonyl)imide salt, a hexafluorophosphate, a compound containing an anion represented by general formula (1), and other components used as needed, in a specific mass ratio in a non-aqueous solvent. The present invention also relates to a method for manufacturing such an electrolyte. Specifically, as an embodiment of the present invention, the method for manufacturing the first electrolyte includes a step of dissolving a bis(fluorosulfonyl)imide salt, a hexafluorophosphate, and a compound containing an anion represented by general formula (1) in a non-aqueous solvent, wherein the mass ratio of hexafluorophosphate to the mass of the bis(fluorosulfonyl)imide salt in the electrolyte is 0.45 or less, and the content of the compound containing an anion represented by general formula (1) in 100% by mass of the electrolyte is 0.03% by mass or more.
[0210] There are no particular limitations on the method of mixing the components or the order of addition; well-known methods can be used. For example, the first electrolyte can be prepared by adding the components to a non-aqueous solvent and mixing them under an inert gas atmosphere.
[0211] [2. Second Electrolyte]
[0212] [2-1. Hexafluorophosphates, bis(fluorosulfonyl)imide salts and compounds containing anions represented by general formula (2)]
[0213] In one embodiment of the present invention, the non-aqueous electrolyte (hereinafter sometimes referred to as "second electrolyte") is a non-aqueous electrolyte containing hexafluorophosphate, bis(fluorosulfonyl)imide salt and a compound containing anion represented by the following general formula (2), wherein the mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is 1 or less, and the content of the compound containing anion represented by general formula (2) is 0.01% by mass or more in 100% by mass of the electrolyte.
[0214] R 2 SO3 - (2)
[0215] (R 2 This indicates an alkyl group having 1 to 3 carbon atoms that may be optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that may be optionally substituted with a halogen atom.
[0216] Hexafluorophosphate is a salt formed by the hexafluorophosphate anion and the counter cation.
[0217] Bis(fluorosulfonyl)imide salts are salts formed by the bis(fluorosulfonyl)imide anion and the counter cation.
[0218] The cations constituting hexafluorophosphate and bis(fluorosulfonyl)imide salt are preferably alkali metal cations such as lithium, sodium, and potassium, and more preferably lithium cations.
[0219] In the above general formula (2), R 2 This indicates an alkyl group having 1 to 3 carbon atoms that may be optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that may be optionally substituted with a halogen atom. As R 2 Preferably, it is an alkoxy group with 1 to 3 carbon atoms that is optionally substituted with a halogen atom, more preferably an aliphatic saturated alkoxy group with 1 to 3 carbon atoms, and particularly preferably an aliphatic saturated alkoxy group with 1 to 2 carbon atoms.
[0220] The halogen atom mentioned above is preferably a fluorine atom.
[0221] The alkoxy group mentioned above is preferably ethoxy or methoxy.
[0222] In general formula (2), in R 2With the aforementioned suitable structure, the tendency to further suppress self-discharge and heat generation within the battery can be further effectively suppressed.
[0223] Compounds containing anions represented by general formula (2) are usually acids (e.g., those with R...). 2 An acid (represented by SO3H) or a salt (a salt formed by an anion represented by general formula (2) and a counter cation), preferably a salt. As a counter cation, an alkali metal cation such as lithium, sodium, or potassium is preferred, and lithium cation is more preferred.
[0224] The concentration of hexafluorophosphate in the non-aqueous electrolyte is typically 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and most preferably 2% by mass or more. It is also typically 18% by mass or less, preferably 16% by mass or less, more preferably 14% by mass or less, further preferably 11% by mass or less, even more preferably 9% by mass or less, still more preferably 7% by mass or less, particularly preferably 6% by mass or less, and most preferably 5% by mass or less. When the concentration of hexafluorophosphate in the non-aqueous electrolyte is within the above range, it tends to suppress battery self-discharge.
[0225] Relative to the total amount of non-aqueous electrolyte, the concentration of bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is typically 3.5% by mass or more, preferably 5% by mass or more, more preferably 7% by mass or more, further preferably 8% by mass or more, particularly preferably 9% by mass or more, and most preferably 10% by mass or more. Additionally, it is typically 25% by mass or less, preferably 22% by mass or less, more preferably 20% by mass or less, particularly preferably 17% by mass or less, and most preferably 15% by mass or less. When the concentration of bis(fluorosulfonyl)imide salt is within the above-mentioned range, there is a tendency for improved thermal stability of the battery.
[0226] Relative to the total amount of the non-aqueous electrolyte, the concentration of the compound containing the anion represented by general formula (2) in the non-aqueous electrolyte is 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.2% by mass or more, and most preferably 0.5% by mass or more. It is generally 10% by mass or less, preferably 5% by mass or less, more preferably 4% by mass or less, particularly preferably 3% by mass or less, and most preferably 2.5% by mass or less. When the concentration of the compound containing the anion represented by general formula (2) in the non-aqueous electrolyte is within the above-mentioned range, it tends to suppress battery self-discharge and heat generation.
[0227] The mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is 1 or less, specifically 0.80 or less, more specifically 0.60 or less, even more specifically 0.50 or less, preferably 0.45 or less, more preferably 0.40 or less, even more preferably 0.35 or less, even more preferably 0.30 or less, particularly preferably 0.25 or less, and most preferably 0.20 or less. Additionally, it is generally 0.01 or more, preferably 0.04 or more, more preferably 0.06 or more, particularly preferably 0.1 or more, and most preferably 0.13 or more. When the mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the non-aqueous electrolyte is within the above range, it tends to suppress battery self-discharge and heat generation.
[0228] The mass ratio of the compound containing the anion represented by general formula (2) in the non-aqueous electrolyte to the mass of the bis(fluorosulfonyl)imide salt is not particularly limited, but is generally 3.7 or less, preferably 2.6 or less, more preferably 1.6 or less, further preferably 0.8 or less, particularly preferably 0.4 or less, and most preferably 0.3 or less. Additionally, it is generally 0.0001 or more, preferably 0.0005 or more, more preferably 0.001 or more, particularly preferably 0.002 or more, and most preferably 0.003 or more. When the mass ratio of the compound containing the anion represented by general formula (2) in the non-aqueous electrolyte to the mass of the bis(fluorosulfonyl)imide salt is within the above range, it tends to suppress self-discharge and heat generation within the battery.
[0229] The identification and content determination of the above-mentioned compounds in non-aqueous electrolytes were performed using ion chromatography and nuclear magnetic resonance (NMR) spectrophotometry.
[0230] In the second electrolyte, the bis(fluorosulfonyl)imide salt is preferably LiN(FSO2)2, the hexafluorophosphate is preferably LiPF6, and the compound containing the anion represented by general formula (2) is preferably the compound represented by the following general formula (2-1).
[0231] LiR 2 SO3 (2-1)
[0232] (R in general formula (2-1) 2 R in general formula (2) 2 (The methods for optimization are the same.)
[0233] The masses of LiN(FSO2)2, LiPF6, and the compounds represented by general formula (2-1) in the second electrolyte, and their mass ratios, are preferably within the ranges described above, as well as the masses of bis(fluorosulfonyl)imide salt, hexafluorophosphate, and compounds containing anions represented by general formula (2).
[0234] [2-2. Other Electrolytes]
[0235] Lithium salts
[0236] Lithium salts are commonly used as electrolytes in non-aqueous electrolytes, excluding bis(fluorosulfonyl)imide salts, hexafluorophosphates, and compounds containing anions represented by general formula (2). No particular restriction is placed on the use of any lithium salt known to be suitable for this application. Lithium salts can be used alone or in combination of two or more. Specific examples are the same as those described above for the lithium salts in the first electrolyte, and the preferred methods are also the same.
[0237] The total content of electrolytes in the non-aqueous electrolyte (the total content of bis(fluorosulfonyl)imide salt, hexafluorophosphate, compounds containing anions represented by general formula (2), and other electrolytes) is not particularly limited, but is generally 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, and generally 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less, relative to the total amount of the non-aqueous electrolyte. When the electrolyte content is within the above range, the conductivity can be adapted to battery operation, and therefore there is a tendency to obtain sufficient output characteristics.
[0238] [2-3. Non-aqueous solvents]
[0239] The second electrolyte is similar to a typical non-aqueous electrolyte, usually containing a non-aqueous solvent in which the electrolyte described above is dissolved as its main component. The non-aqueous solvent used only needs to dissolve the electrolyte and is not particularly limited; known organic solvents can be used. One organic solvent can be used alone, or two or more can be used in combination. Specific examples are the same as those described above for the first electrolyte, and the preferred methods are also the same. Specific examples of combinations of two or more non-aqueous solvents are also the same as those described above for the first electrolyte, and the preferred methods are also the same. The preferred ranges for the content of each non-aqueous solvent are also the same as those described above for the first electrolyte.
[0240] [2-4. Additives]
[0241] The second electrolyte may contain various additives without significantly impairing the effects of the present invention. Any conventionally known additives may be used. It should be noted that an additive may be used alone, or two or more may be used in any combination and ratio.
[0242] Examples of additives optionally included in non-aqueous electrolytes include at least one compound (A) selected from the following: cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, non-fluorinated carboxylic esters, cyclic compounds having ether bonds, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, compounds containing borate anions, compounds containing phosphate anions having P=O and PF bonds, and compounds containing oxalate complex anions (excluding bis(fluorosulfonyl)imide salts, hexafluorophosphates, and compounds represented by general formula (2-1)). Specific examples of these include the compounds described in the first electrolyte, such as those listed in International Publication No. 2015 / 111676.
[0243] Compound (A) is preferably selected from at least one compound selected from cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, cyclic compounds having ether bonds, non-fluorinated carboxylic acid esters, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, boron-containing anions, compounds containing oxalate complex anions, and compounds containing phosphate anions having P=O bonds and PF bonds (excluding bis(fluorosulfonyl)imide salts, hexafluorophosphates, and compounds containing anions represented by general formula (2)).
[0244] Preferably, the compound is selected from at least one anion-containing compound (hereinafter also referred to as "the compound containing a specific anion"), which is selected from compounds containing phosphate anions having PF bonds and P=O bonds, and compounds containing oxalate complex anions, and / or at least one carbonate compound (hereinafter also referred to as "the specific carbonate compound") selected from cyclic carbonates having carbon-carbon unsaturated bonds and fluorinated cyclic carbonates.
[0245] The content of the additive is not particularly limited, as long as it does not significantly impair the effect of the present invention, and is arbitrary. Relative to the total amount of non-aqueous electrolyte, it is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, and particularly preferably less than 1% by mass.
[0246] The preferred ranges for the content of each additive are the same as those for the first electrolyte.
[0247] (The mass ratio of compounds containing a specific anion to compounds containing anion represented by general formula (2))
[0248] The mass ratio of the content of the compound containing the specific anion (total amount when there are two or more) to the content of the compound containing the anion represented by general formula (2) (compound containing the specific anion [g] / compound containing the anion represented by general formula (2) [g]) is generally 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and generally 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. The mass ratio of the content of the compound containing the specific anion to the content of the compound represented by general formula (2-1) (compound containing the specific anion [g] / compound represented by general formula (2-1) [g]) is also preferably within the same range as described above.
[0249] When the mass ratio is within the range described above, the battery characteristics, especially the resistance retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. The reason for this is not yet clear, but it can be considered that by including compounds containing anions represented by general formula (2) and compounds containing specific anions within the range described above mass ratio, the side reactions of the non-aqueous electrolyte components on the electrode surface can be suppressed to a minimum.
[0250] (The mass ratio of a specific carbonate compound to a compound containing an anion represented by general formula (2))
[0251] The mass ratio of the content of a specific carbonate compound (two or more, total amount) to the content of the compound containing the anion represented by general formula (2) (specific carbonate compound [g] / compound containing the anion represented by general formula (2) [g]) is generally 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and even more preferably 0.5 or more. It is also generally 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. The mass ratio of the content of the specific carbonate compound to the content of the compound represented by general formula (2-1) (specific carbonate compound [g] / compound represented by general formula (2-1) [g]) is also preferably within the same range as described above. When the mass ratio is within the above range, battery characteristics, especially durability, can be improved. The reason is not yet clear, but it can be considered that by containing a specific carbonate compound within the above mass ratio range, a film can be formed on the electrode, minimizing the side reactions of non-aqueous electrolyte components.
[0252] [2-5. Electrolyte manufacturing method]
[0253] The second electrolyte can be manufactured by dissolving bis(fluorosulfonyl)imide salt, hexafluorophosphate, a compound containing an anion represented by general formula (2), and other components used as needed, in a specific mass ratio in a non-aqueous solvent. The present invention also relates to a method for manufacturing such an electrolyte. Specifically, a method for manufacturing an electrolyte according to one embodiment of the present invention includes the step of dissolving bis(fluorosulfonyl)imide salt, hexafluorophosphate, and a compound containing an anion represented by general formula (2) in a non-aqueous solvent, wherein the mass ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt in the electrolyte is 1 or less, and the content of the compound containing an anion represented by general formula (2) in 100% by mass of the electrolyte is 0.01% by mass or more.
[0254] There are no particular limitations on the method of mixing the components or the order of addition; well-known methods can be used. For example, the second electrolyte can be prepared by adding the components to a non-aqueous solvent and mixing them under an inert gas atmosphere.
[0255] [3. Battery]
[0256] As one embodiment of the present invention, the battery (non-aqueous electrolyte secondary battery) is a non-aqueous electrolyte secondary battery having a positive electrode with a positive electrode active material capable of absorbing and releasing metal ions and a negative electrode active material capable of absorbing and releasing metal ions, and having a non-aqueous electrolyte.
[0257] [3-1. Non-aqueous electrolyte]
[0258] The first or second electrolyte described above is used as the non-aqueous electrolyte. It should be noted that, without departing from the spirit of the invention, other non-aqueous electrolytes may be used in combination with the described non-aqueous electrolyte.
[0259] [3-2. Positive electrode]
[0260] At least a portion of the surface of the current collector has positive electrode active material.
[0261] [3-2-1. Positive Electrode Active Material]
[0262] The following describes the positive electrode active material (lithium transition metal compound) used in the positive electrode.
[0263] [3-2-1-1. Lithium transition metal compounds]
[0264] Lithium transition metal compounds refer to compounds that have a structure capable of inserting and deintercalating lithium ions, such as sulfides, phosphate compounds, silicate compounds, borate compounds, and lithium transition metal complex oxides. Among these, phosphate compounds and lithium transition metal complex oxides are preferred, and lithium transition metal complex oxides are more preferred.
[0265] Examples of lithium transition metal composite oxides include spinel structures that enable three-dimensional diffusion and layered structures that enable two-dimensional diffusion of lithium ions.
[0266] Lithium transition metal composite oxides with spinel structures are typically represented by the following compositional formula.
[0267] Li x’ M'2O4 (In the above composition formula, x' is 1≤x'≤1.5, and M' contains at least one transition metal element.)
[0268] Specific examples include: LiMn2O4, LiCoMnO4, and LiNi. 0.5 Mn 1.5 O4, LiCoVO4, etc.
[0269] Lithium transition metal composite oxides with layered structures are usually represented by the following composition formula (3).
[0270] Li 1+x MO2···(3)
[0271] (In composition formula (3), x is -0.1≤x≤0.5, and M contains at least one transition metal element.)
[0272] In composition (3), M is preferably at least one element selected from Ni, Co, Mn, Al, Mg, Zr, Fe, Ti, V, Cr, La, Ce, Mo, Sc, Y, and Er, and preferably contains at least Ni. The Ni content in M is preferably 30 mol% or more, more preferably 45 mol% or more, further preferably 55 mol% or more, particularly preferably 65 mol% or more, and most preferably 75 mol% or more.
[0273] Specific examples include: LiCoO2, LiNiO2, and LiNi. 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.05 Ni 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 1Mn0.19 Co 0.20 O2, LiNi 0.83 Mn 0.06 Co 0.11 O2, Li 1.05 Ni 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, Li[Li 1 / 3 Mn 2 / 3 O2 and its solid solutions, etc.
[0274] From the viewpoint of improving battery capacity, lithium transition metal composite oxides with a layered structure are preferred, and transition metal composite oxides represented by the following composition formula (3-1) are more preferred.
[0275] Li a1 Ni b1 M c1 O2 ··· (3-1)
[0276] (In formula (3-1), a1, b1, and c1 represent values that satisfy 0.90≤a1≤1.10, 0.30≤b1≤0.98, and 0.01≤c1≤0.5, respectively. M represents at least one element selected from Co, Mn, Al, Mg, Zr, Fe, Ti, V, Cr, La, Ce, Mo, Sc, Y, and Er.)
[0277] In composition (3-1), b1 preferably satisfies 0.4≤b1, more preferably satisfies 0.5≤b1, and particularly preferably satisfies 0.6≤b1. In addition, in composition (3-1), 0.50≤b1+c1 is preferred, more preferably 0.50≤b1+c1≤1, and even more preferably b1+c1=1.
[0278] In particular, from the viewpoint of the structural stability of lithium transition metal composite oxides, the transition metal oxide represented by the following composition formula (3-2) is preferred.
[0279] Li a2 Ni b2 Co c2 M d2 O2··· (3-2)
[0280] (In formula (3-2), a2, b2, and c2 represent values that satisfy 0.90≤a2≤1.10, 0.50≤b2≤0.98, and 0.01≤c2<0.50, respectively, and satisfy 0.01≤d2<0.50. M represents at least one element selected from Mn, Al, Mg, Zr, Fe, Ti, V, Cr, La, Ce, Mo, Sc, Y, and Er.)
[0281] In formula (3-2), M preferably contains Mn or Al, and more preferably Mn. This is because it improves the structural stability of the lithium transition metal oxide and suppresses structural degradation during repeated charge and discharge. Furthermore, in formula (3-2), b² + c² + d² = 1 is preferred.
[0282] Suitable specific examples of lithium transition metal oxides represented by formula (3-2) include, for example, LiNi. 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.50 Co 0.20 Mn 0.30 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.61 Mn 0.19 Co 0.20 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.83 Mn 0.06 Co 0.11 O2, etc.
[0283] Phosphate compounds are usually represented by the following formula.
[0284] Li x "M" y PO4
[0285] (In the above composition formula, 0.8≤x”≤1.5, 0.9≤y”≤1.1, and M” contains at least one transition metal element.)
[0286] Examples of "M" include Fe, Ni, Co, and Mn.
[0287] As a phosphate compound, it is particularly preferred to be a compound represented by the following formula (4).
[0288] LiMn 1-y Fe y PO4 (4)
[0289] (In the composition formula (4), y satisfies 0) <y≤1。)
[0290] Suitable specific examples of phosphate compounds represented by formula (4) include, for example, LiFePO4 and LiMn. 0.6 Fe 0.4 PO4, etc.
[0291] [3-2-1-2. Importing Heterogeneous Elements]
[0292] In addition, lithium transition metal composite oxides can incorporate elements other than those included in the above-mentioned composition (dissimilar elements).
[0293] [3-2-1-3. Surface Coating]
[0294] A substance with a different composition than the positive electrode active material (a surface-attached substance) can be attached to the surface of the aforementioned positive electrode active material. Examples of surface-attached substances include: oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate.
[0295] These surface-adhering substances can be attached to the surface of the positive electrode active material, for example, by dissolving or suspending them in a solvent and impregnating them with the positive electrode active material, or by drying them.
[0296] The amount of surface-attached material relative to the positive electrode active material is preferably 1 μmol / g or more, and more preferably 10 μmol / g or more, and is usually used at 1 mmol / g or less.
[0297] In this specification, the substance on which the above-mentioned surface-attached substance is attached to the surface of the positive electrode active material will also be referred to as the "positive electrode active material".
[0298] [3-2-1-4. Mixing]
[0299] It should be noted that these positive electrode active materials can be used alone, or two or more can be used in any combination and ratio.
[0300] [3-2-2. Composition and Manufacturing Method of Positive Electrode]
[0301] The composition and manufacturing method of the positive electrode are described below. In this embodiment, the positive electrode using the positive electrode active material can be manufactured by conventional methods. That is, the positive electrode active material, binder, and conductive materials and thickeners as needed can be dry-mixed to form a sheet, which is then pressed onto the positive electrode current collector; or the positive electrode can be obtained by coating, which involves dissolving or dispersing these materials in a liquid medium such as an aqueous solvent or an organic solvent to form a slurry, coating it onto the positive electrode current collector and drying it to form a layer of positive electrode active material on the current collector. Alternatively, for example, the above-mentioned positive electrode active material can be rolled to form a sheet electrode, or it can be compressed to form a granular electrode.
[0302] The following describes the process of coating and drying the slurry on the positive electrode current collector.
[0303] [3-2-2-1. Content of active substances]
[0304] In the positive electrode active material layer, the content of positive electrode active material is usually above 80% by mass and below 99.5% by mass.
[0305] [3-2-2-2. Conductive Materials]
[0306] As a conductive material, any known conductive material can be used. Specific examples include: metallic materials such as copper and nickel; graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; carbonaceous materials such as needle coke and amorphous carbon; etc. A single conductive material can be used, or two or more materials can be combined in any combination and ratio. The conductive material can be used in a manner that typically contains 0.01% by mass or more and 50% by mass or less in the positive electrode active material layer.
[0307] [3-2-2-3. Adhesive]
[0308] As a binder used in the manufacture of the positive electrode active material layer, for example, in the case of forming the positive electrode active material layer by coating method, any material that can be dissolved or dispersed in the liquid medium used for slurry is acceptable, and there is no particular limitation on its type. From the viewpoints of weather resistance, chemical resistance, heat resistance, and flame retardancy, fluorinated resins such as polyvinylidene fluoride, polyvinylidene fluoride, and polytetrafluoroethylene, as well as CN-containing polymers such as polyacrylonitrile and polyvinylidene cyanide are preferred.
[0309] Alternatively, mixtures, modifiers, derivatives, random copolymers, alternating copolymers, graft copolymers, block copolymers, etc., of the aforementioned polymers can also be used. It should be noted that the adhesive can be used alone, or two or more can be combined in any combination and ratio.
[0310] Furthermore, when using resin as a binder, the weight-average molecular weight of the resin is arbitrary as long as it does not significantly impair the effects of the present invention. It is typically 10,000 or more, preferably 50,000 or more, and particularly preferably 100,000 or more. On the other hand, it is typically 3,000,000 or less, preferably 950,000 or less, and particularly preferably 900,000 or less. When the molecular weight is within this range, the strength of the electrode is improved, and the electrode can be appropriately formed.
[0311] The proportion of binder in the positive electrode active material layer is usually above 0.1% by mass and below 80% by mass.
[0312] [3-2-2-4. Current collector]
[0313] There are no particular restrictions on the material used for the positive electrode current collector; any known material can be used. Specific examples include aluminum, stainless steel, nickel plating, titanium, tantalum, and other metallic materials. Aluminum is preferred.
[0314] Examples of current collector shapes include: metal foil, metal cylinder, metal coil, metal plate, metal film, expanded alloy, perforated metal plate, and foamed metal. Among these, metal foil or metal film is preferred. It should be noted that the metal film can be suitably shaped into a mesh.
[0315] When the current collector of the positive electrode is in the shape of a plate, film, etc., the thickness of the current collector is arbitrary, but it is usually above 1 μm and below 1 mm.
[0316] [3-2-2-5. Thickness of the positive electrode plate]
[0317] There is no particular limitation on the thickness of the positive electrode plate. From the perspective of high capacity and high output, the thickness of the positive electrode active material layer obtained by subtracting the thickness of the current collector from the thickness of the positive electrode plate is usually more than 10 μm and less than 500 μm, relative to the single side of the current collector.
[0318] [3-2-2-6. Electrode Density]
[0319] To increase the filling density of the positive electrode active material, the positive electrode active material layer obtained by coating and drying is preferably compacted using a manual press or roller press. The density of the positive electrode active material layer on the current collector is typically 1.5 g / cm³. 3 Above and 4.5g / cm 3 the following.
[0320] [3-2-2-7. Surface coating of the positive electrode plate]
[0321] In addition, the above-mentioned positive electrode plate can be a positive electrode plate on which a substance with a different composition from the positive electrode plate is attached to its surface. As such a substance, the same substance as the surface-attached substance optionally attached to the surface of the positive electrode active material can be used.
[0322] [3-3. Negative electrode]
[0323] At least a portion of the current collector surface has a negative electrode active material.
[0324] [3-3-1. Negative Electrode Active Material]
[0325] As a negative electrode active material, any material capable of electrochemically adsorbing / releasing metal ions is acceptable, with no particular limitations. Specific examples include: carbonaceous materials, materials containing metal elements and / or half-metal elements capable of alloying with Li, materials containing lithium metal composite oxides, alkali metals, and mixtures thereof. From the viewpoint of good cycle characteristics, safety, and excellent continuous charging characteristics, carbonaceous materials, materials containing metal elements and / or half-metal elements capable of alloying with Li, and mixtures of materials containing metal elements and / or half-metal elements capable of alloying with Li and carbonaceous materials are preferred. These can be used individually or in any combination of two or more.
[0326] [3-3-1-1. Carbonaceous Materials]
[0327] Examples of carbonaceous materials include: natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. Natural graphite is preferred. A single carbonaceous material can be used alone, or two or more materials can be combined in any combination and ratio.
[0328] Examples of natural graphite include: scaly graphite, flake graphite, and / or graphite particles that have undergone spheroidization, densification, or other treatments. Among these, spherical or ellipsoidal graphite particles that have undergone spheroidization treatment are particularly preferred from the viewpoint of particle filling capacity or charge / discharge rate characteristics.
[0329] The average particle size (d50) of graphite particles is typically greater than 1 μm and less than 100 μm.
[0330] [3-3-1-2. Physical Properties of Carbonaceous Materials]
[0331] The carbonaceous material used as the negative electrode active material preferably satisfies at least one of the physical properties and shape characteristics shown in (1) to (4) below, and it is particularly preferred that it satisfies multiple characteristics at the same time.
[0332] (1) X-ray diffraction parameters
[0333] The d-value (interlayer spacing) of the lattice plane (002 plane) of carbonaceous materials, determined by X-ray diffraction based on the vibratory method, is typically 0.335 nm or more and 0.360 nm or less. Furthermore, the crystallite size (Lc) of carbonaceous materials, determined by X-ray diffraction based on the vibratory method, is typically 1.0 nm or more.
[0334] (2) Volume-based average particle size
[0335] The volume-based average particle size of carbonaceous materials is the average particle size (median particle size) of the volume-based standard obtained by laser diffraction / scattering method, which is usually above 1 μm and below 100 μm.
[0336] (3) Raman R value, Raman half-width
[0337] The Raman R value of carbonaceous materials is determined by argon-ion laser Raman spectroscopy, and is typically above 0.01 and below 1.5.
[0338] In addition, the 1580cm of carbonaceous material -1 There is no particular limitation on the width of the Raman half-value in the vicinity; it is usually 10 cm. -1 Above and 100cm -1 the following.
[0339] (4) BET specific surface area
[0340] The BET specific surface area of carbonaceous materials is the value of the specific surface area measured using the BET method, typically 0.1 m². 2 ·g -1 Above and 100m 2 ·g -1 the following.
[0341] The negative electrode active material can contain two or more carbonaceous materials with different properties. The properties referred to here are X-ray diffraction parameters, volume-based average particle size, Raman R value, Raman half-width, and BET specific surface area.
[0342] Preferred examples include: when the median particle size is the center, the volumetric reference particle size distribution does not exhibit left-right symmetry; it contains two or more carbonaceous materials with different Raman R values; and it contains two or more carbonaceous materials with different X-ray parameters.
[0343] [3-3-1-3. Materials containing metallic and / or semi-metallic elements capable of alloying with Li]
[0344] As the material containing a metal element and / or metalloid element capable of alloying with Li, any conventionally known material can be used. From the viewpoints of capacity and cycle life, for example, a simple substance of a metal and / or metalloid element selected from Sb, Si, Sn, Al, As and Zn, which may be optionally coated with carbon, or a compound thereof is preferred. In addition, when the material containing a metal element and / or metalloid element capable of alloying with Li contains two or more elements, this material may be an alloy material formed from an alloy of these metals.
[0345] Further, examples of the material containing a metal element and / or metalloid element capable of alloying with Li include oxides, nitrides, carbides and the like. These materials may contain two or more metal elements and / or metalloid elements capable of alloying with Li.
[0346] Among these, from the viewpoint of increasing capacity, metallic Si (hereinafter sometimes referred to as Si) or a Si-containing inorganic compound is preferred.
[0347] Further, the material containing a metal element and / or metalloid element capable of alloying with Li may have already been alloyed with Li during the production of the negative electrode described later.
[0348] In the present specification, Si or Si-containing inorganic compounds are collectively referred to as Si compounds. Specific examples of the Si compound include SiO x (0≤x≤2) and the like. Specific examples of the metal compound alloyed with Li include Li y Si (0<y≤4.4), Li₂SiO 2+z (0<z≤2) and the like. As the Si compound, from the viewpoint that the theoretical capacity is larger than that of graphite, a Si oxide (SiO x1 , 0<x1≤2) is preferred, or from the viewpoint that alkali ions such as lithium ions are easily intercalated and deintercalated and a high capacity can be obtained, amorphous Si or nano-sized Si crystals are preferred.
[0349] When the material containing a metal element and / or metalloid element capable of alloying with Li is in the form of particles, the average particle diameter (d50) thereof is usually 0.01 μm or more and 10 μm or less from the viewpoint of cycle life.
[0350] [3-3-1-4. Mixture of particles of material containing metal element and / or metalloid element capable of alloying with Li and graphite particles]
[0351] The mixture of graphite particles and materials containing metal elements and / or semi-metal elements capable of alloying with Li, used as a negative electrode active material, can be a mixture formed by mixing the aforementioned materials containing metal elements and / or semi-metal elements capable of alloying with Li with the aforementioned graphite particles in a state of independent material particles, or it can be a composite in which the materials containing metal elements and / or semi-metal elements capable of alloying with Li exist on the surface or inside of the graphite particles.
[0352] The proportion of particles containing metallic and / or semi-metallic elements capable of alloying with Li to the total proportion of particles containing metallic and / or semi-metallic elements capable of alloying with Li and graphite particles is typically 1% by mass or more and 99% by mass or less.
[0353] [3-3-1-5. Lithium-containing metal composite oxide materials]
[0354] The lithium-containing metal composite oxide material used as the negative electrode active material is not particularly limited as long as it can absorb and release lithium ions. From the viewpoint of high current density charge and discharge characteristics, lithium-containing metal composite oxide materials containing titanium are preferred, and lithium-titanium composite oxides (hereinafter sometimes simply referred to as "lithium-titanium composite oxides") are more preferred. Lithium-titanium composite oxides with spinel structure are particularly preferred because they can significantly reduce output resistance.
[0355] In addition, the lithium and / or titanium in the lithium-titanium composite oxide can be replaced by other metallic elements, such as at least one element selected from Al, Ga, Cu and Zn.
[0356] Li is preferred as a lithium-titanium composite oxide. 4 / 3 Ti 5 / 3 O4, Li1Ti2O4 and Li 4 / 5 Ti 11 / 5 O4. Additionally, lithium-titanium composite oxides, in which lithium and / or titanium are replaced by other elements, preferably Li, are used. 4 / 3 Ti 4 / 3 Al 1 / 3 O4.
[0357] [3-3-2. Composition and Manufacturing Method of the Negative Electrode]
[0358] The negative electrode can be manufactured by any known method, provided that the effect of the present invention is not significantly impaired. For example, it can be manufactured by adding a binder, aqueous solvent or organic solvent or other liquid medium to the negative electrode active material, adding a thickener, conductive material, filler or other material as needed, to form a slurry, coating it onto a current collector, drying it and pressing it to form a negative electrode active material layer.
[0359] [3-3-2-1. Content of active substances]
[0360] The content of negative electrode active material in the negative electrode active material layer is usually above 80% by mass and below 99.5% by mass.
[0361] [3-3-2-2. Electrode Density]
[0362] To increase the filling density of the negative electrode active material, the negative electrode active material layer obtained by coating and drying is preferably compacted using a manual press or roller press. There are no particular restrictions on the electrode structure when polarizing the negative electrode active material; the density of the negative electrode active material layer on the current collector is typically 1 g·cm³. -3 Above and 2.2 g·cm -3 the following.
[0363] [3-3-2-3. Tackifiers]
[0364] Thickeners are typically used to adjust the viscosity of slurries. There are no particular limitations on thickeners; examples include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, and their salts. These can be used individually or in combination or ratios of two or more.
[0365] When using a tackifier, the ratio of the tackifier to the negative electrode active material is typically 0.1% by mass or more and 5% by mass or less.
[0366] [3-3-2-4. Adhesive]
[0367] As a binder for bonding negative electrode active materials, any material that is stable to non-aqueous electrolytes and liquid media used in electrode manufacturing is acceptable; there are no particular restrictions.
[0368] Specific examples include: SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), ethylene-propylene rubber, and other rubber-like polymers; polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-ethylene copolymer, and other fluorinated polymers. These can be used individually or in combination or ratios of two or more.
[0369] The ratio of binder to negative electrode active material is typically 0.1% by mass or more and 20% by mass or less.
[0370] Especially when the binder contains rubber-like polymers such as SBR as its main component, the ratio of the binder to the negative electrode active material is preferably 0.1% by mass or more and 5% by mass or less. Furthermore, when the binder contains fluorinated polymers such as polyvinylidene fluoride as its main component, the ratio of the binder to the negative electrode active material is preferably 1% by mass or more and 15% by mass or less.
[0371] [3-3-2-5. Current collector]
[0372] As the current collector for maintaining the active material of the negative electrode, any known current collector can be used. Examples of current collectors for the negative electrode include: aluminum, copper, nickel, stainless steel, nickel-plated steel, and other metallic materials. From the viewpoint of ease of processing and cost, copper is particularly preferred.
[0373] Examples of current collector shapes include: metal foil, metal cylinder, metal coil, metal plate, metal film, expanded alloy, perforated metal plate, and foamed metal. Among these, metal foil or metal film is preferred. It should be noted that metal foil and metal film can be appropriately shaped into a mesh.
[0374] When the current collector of the negative electrode is in the shape of a plate, film, etc., the thickness of the current collector is arbitrary, usually above 1μm and below 1mm.
[0375] [3-3-2-6. Thickness of the negative electrode plate]
[0376] The thickness of the negative electrode (also known as the "negative electrode plate") is designed according to the positive electrode used and there is no particular limitation. The thickness of the negative electrode active material layer, obtained by subtracting the current collector thickness from the thickness of the negative electrode material, is usually above 15 μm and below 300 μm.
[0377] [3-3-2-7. Surface coating of negative electrode plate]
[0378] Alternatively, a negative electrode plate can be used in which a substance with a different composition from the negative electrode active material (a surface-attached substance) is attached to its surface. Examples of surface-attached substances include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate.
[0379] [3-4. Diaphragm]
[0380] To prevent short circuits, a diaphragm is typically placed between the positive and negative electrodes. In this case, a non-aqueous electrolyte is usually used while impregnated within the diaphragm.
[0381] There are no particular restrictions on the material or shape of the diaphragm, as long as it does not significantly impair the effect of the present invention, any known diaphragm can be used.
[0382] [3-5. Battery Design]
[0383] [3-5-1. Electrode Assembly]
[0384] The electrode assembly can be any structure, either a stacked structure formed by sandwiching the positive and negative electrode plates with the separator, or a spiral structure formed by sandwiching the positive and negative electrode plates with the separator. The volume of the electrode assembly typically accounts for more than 40% and less than 90% of the battery's internal volume.
[0385] [3-5-2. Collector Structure]
[0386] When the electrode assembly has the aforementioned stacked structure, a structure formed by assembling and soldering the metal core portions of each electrode layer to a terminal can be used appropriately. Alternatively, a structure that reduces resistance by providing multiple terminals within the electrode can also be used appropriately. When the electrode assembly has the aforementioned wound structure, multiple lead structures can be provided at both the positive and negative electrodes and converged to a terminal, thereby reducing internal resistance.
[0387] [3-5-3. Protective Components]
[0388] As protective components, PTC (Positive Temperature Coefficient) elements that generate heat and increase resistance due to excessive current, thermal fuses, thermistors, and valves (current cut-off valves) that cut off the current flowing in the circuit due to a rapid increase in internal pressure and temperature of the battery when abnormal heating occurs can be used. The protective components are preferably those that do not operate under conditions of normal high-current use, and more preferably designed so that abnormal heating or thermal runaway will not occur even without the protective components.
[0389] [3-5-4. Exterior body]
[0390] Non-aqueous electrolyte secondary batteries are typically constructed by housing the aforementioned non-aqueous electrolyte, negative electrode, positive electrode, and separator within an outer casing. There are no limitations on this outer casing; any known casing can be used as long as it does not significantly impair the effectiveness of the invention.
[0391] The material of the outer casing can be any substance that is stable to the non-aqueous electrolyte used, without any particular limitation. From the perspective of lightweighting, aluminum or aluminum alloy metal or laminated film can be used appropriately.
[0392] Among the metal casings used above, examples include casings that form a sealed structure by fusing metals together through laser welding, resistance welding, or ultrasonic welding, or casings that use the metals with the aid of resin gaskets to form a riveted structure.
[0393] [3-5-5. Shape]
[0394] In addition, the shape of the outer shell is also arbitrary, such as cylindrical, square, laminated, button-shaped, large, or any other shape.
[0395] [3-6. Battery Manufacturing Methods]
[0396] As one embodiment of the present invention, a battery can be manufactured by housing a positive electrode, a negative electrode, and other materials as needed into an outer casing, and then injecting the electrolyte of the present invention into the outer casing. The present invention also relates to a method for manufacturing such a battery. That is, a method for manufacturing a battery as one embodiment of the present invention includes: a step of housing a positive electrode and a negative electrode into an outer casing, and a step of injecting the electrolyte of the present invention into the outer casing.
[0397] [4. Applications]
[0398] The electrolyte and battery, as one embodiment of the present invention, can be used in a wide range of applications, from so-called consumer power supplies such as those for laptops to vehicle power supplies for automobiles. In particular, the electrolyte of the present invention simultaneously improves the thermal stability of the battery and suppresses self-discharge, thus making it suitable for use as a vehicle power supply for vehicles and the like. That is, according to the present invention, a vehicle comprising a battery according to one embodiment of the present invention can be suitably provided.
[0399] Example
[0400] The present invention will be further described in detail below with examples and comparative examples, but the present invention is not limited to these examples.
[0401] <Examples A-1~14, Comparative Examples A-1~3>
[0402] [Preparation of non-aqueous electrolytes]
[0403] Under a dry argon atmosphere, LiPF6 (as a hexafluorophosphate), LiN(FSO2)2 (hereinafter sometimes referred to as "LiFSI") (as a bis(fluorosulfonyl)imide salt), LiFSO3 (as a compound containing an anion represented by general formula (1), and other compounds listed in Table 1 (LiBOB (lithium bis(oxalate)borate), LiPO2F2, VC (ethylene carbonate)) were dissolved in a mixture of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) to achieve the concentrations listed in Table 1, as measured by the concentrations in the non-aqueous electrolyte. It should be noted that in Tables 1-3, "compound (1)" refers to a compound containing an anion represented by general formula (1).
[0404] Fabrication of non-aqueous electrochemical battery cells
[0405] Will be used as the positive electrode of aluminum foil (12cm) 2A negative electrode (13.4cm) is formed by pressing lithium foil onto copper foil. 2 The separator and polyolefin are stacked in the order of negative electrode, separator, and positive electrode. The resulting battery element is wrapped with an aluminum laminate, injected with the above-mentioned non-aqueous electrolyte, and then sealed to produce a sheet-like non-aqueous electrochemical battery cell.
[0406] Evaluation of Non-Aqueous Electrochemical Cells
[0407] [Self-discharge]
[0408] In a constant temperature bath at 25°C, sheet-like non-aqueous electrochemical cells were subjected to a 4V voltage for 24 hours. The charge capacity after charging at a constant voltage of 4.3V for 24 hours was then used as the "self-discharge." Lower self-discharge is considered better.
[0409] Table 1 shows the self-discharge of the embodiments and comparative examples (with comparative example A-1 set as a relative value of 100).
[0410]
[0411] As can be clearly seen from Table 1, for non-aqueous electrolyte secondary batteries that contain hexafluorophosphate, bis(fluorosulfonyl)imide salt and compounds containing anions represented by general formula (1) in specific amounts (Examples A-1 to 14), self-discharge is suppressed compared to non-aqueous electrolytes with a hexafluorophosphate / bis(fluorosulfonyl)imide salt ratio exceeding a specific ratio (Comparative Example A-1), non-aqueous electrolytes without hexafluorophosphate (Comparative Example A-2), and non-aqueous electrolytes without compounds containing anions represented by general formula (1) (Comparative Example A-3).
[0412] <Examples B-1~7, Comparative Examples B-1~3>
[0413] [Preparation of non-aqueous electrolytes]
[0414] Under a dry argon atmosphere, LiPF6 as a hexafluorophosphate, LiFSI as a bis(fluorosulfonyl)imide salt, and LiFSO3 as a compound containing an anion represented by general formula (1) were dissolved in a mixture of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) in a manner that, based on the concentrations recorded in Table 2, were achieved in a non-aqueous electrolyte.
[0415] Using this non-aqueous electrolyte, a non-aqueous electrolyte secondary battery was fabricated using the method described below, and its performance was evaluated.
[0416] [The production of the positive electrode]
[0417] LiNi will be used as the positive electrode active material 0.61 Mn 0.19 Co0.20 90 parts by weight of O2, 7 parts by weight of acetylene black (as a conductive material), and 3 parts by weight of polyvinylidene fluoride (PVdF) (as a binder) were mixed in N-methyl-2-pyrrolidone and slurried. The resulting slurry was uniformly coated onto a 15 μm thick aluminum foil and dried, then rolled to form the positive electrode. It should be noted that the density of the positive electrode active material layer was 3.4 g / cm³. 3 .
[0418] [Making the negative electrode]
[0419] To 49 parts by weight of graphite powder, 50 parts by weight of an aqueous dispersion of sodium carboxymethyl cellulose (sodium carboxymethyl cellulose concentration 1 by weight) as a thickener and 1 part by weight of an aqueous dispersion of styrene-butadiene rubber (styrene-butadiene rubber concentration 50 by weight) as a binder were added, and the mixture was mixed and slurried using a disperser. The resulting slurry was uniformly coated onto a copper foil with a thickness of 10 μm and dried, and then rolled to form a negative electrode.
[0420] Manufacturing of non-aqueous electrolyte secondary batteries
[0421] The above-mentioned positive electrode, negative electrode, and polyolefin separator were stacked in the order of negative electrode, separator, and positive electrode. The resulting battery element was wrapped with an aluminum laminate, and the above-mentioned non-aqueous electrolyte was injected and vacuum-sealed to fabricate a sheet-like non-aqueous electrolyte secondary battery. Using the non-aqueous electrolytes described in Table 2, non-aqueous electrolyte secondary batteries were fabricated, resulting in Examples B-1 to 7 and Comparative Examples B-1 to 3.
[0422] [Evaluation of voltage drop]
[0423] In a constant temperature bath at 25°C, the sheet-shaped non-aqueous electrolyte secondary battery was charged to 3.7V at a constant current of 0.05C (the current value of the rated capacity based on the discharge capacity of 1 hour is set as 1C, and the same applies below), then charged to 4.25V at a constant current-constant voltage of 0.2C, and then discharged to 2.8V at a constant current of 0.2C.
[0424] Furthermore, the voltage drop after storage at 60°C for 24 hours was evaluated by charging to 4.1V at a constant current-constant voltage of 0.2C.
[0425] Table 2 shows the voltage drop of the embodiments and comparative examples (relative values with Comparative Example B-1 set to 100).
[0426]
[0427] As can be clearly seen from Table 2, for non-aqueous electrolyte secondary batteries that contain hexafluorophosphate, bis(fluorosulfonyl)imide salt, and anion containing a compound represented by general formula (1) in a specific amount (Examples B-1 to 7), the voltage drop associated with self-discharge is suppressed compared with non-aqueous electrolytes that do not contain hexafluorophosphate (Comparative Examples B-1 to 2) and non-aqueous electrolytes in which the ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt exceeds a specific ratio (Comparative Example B-3).
[0428] <Examples C-1~5>
[0429] [Preparation of non-aqueous electrolytes]
[0430] Under a dry argon atmosphere, LiPF6 as a hexafluorophosphate, LiFSI as a bis(fluorosulfonyl)imide salt, LiFSO3 as a compound containing an anion represented by general formula (1), and other compounds (VC (ethylene carbonate), LiBOB (lithium bis(oxalate)borate), LiPO2F2) listed in Table 3 were dissolved in a mixture of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) in a manner that, based on the concentrations recorded in Table 3, were achieved using a non-aqueous electrolyte concentration meter.
[0431] Using this non-aqueous electrolyte, a non-aqueous electrolyte secondary battery was fabricated using the method described below, and its performance was evaluated.
[0432] [The production of the positive electrode]
[0433] LiMn will be used as the positive electrode active material 0.6 Fe 0.4 90 parts by weight of PO4, 5 parts by weight of acetylene black (as a conductive material), and 5 parts by weight of polyvinylidene fluoride (PVdF) (as a binder) were mixed in N-methyl-2-pyrrolidone and slurried. The resulting slurry was uniformly coated onto an aluminum foil with a thickness of 15 μm and dried, then rolled to form the positive electrode. It should be noted that the density of the positive electrode active material layer was 1.8 g / cm³. 3 .
[0434] [Making the negative electrode]
[0435] 97.5 parts by weight of graphite powder, 0.7 parts by weight of sodium carboxymethyl cellulose as a tackifier, and 1.8 parts by weight of styrene-butadiene rubber as a binder were mixed in water and slurried. The resulting slurry was uniformly coated onto a copper foil with a thickness of 10 μm and dried, and then rolled to form a negative electrode.
[0436] Manufacturing of non-aqueous electrolyte secondary batteries
[0437] The above-mentioned positive electrode, negative electrode, and polyolefin separator were stacked in the order of negative electrode, separator, and positive electrode. The resulting battery element was wrapped with an aluminum laminate, injected with the above-mentioned non-aqueous electrolyte, and then vacuum-sealed to produce a sheet-like non-aqueous electrolyte secondary battery. Non-aqueous electrolyte secondary batteries were made using the non-aqueous electrolytes described in Table 3, as examples C-1 to C-5.
[0438] [Evaluation of voltage drop]
[0439] In a constant temperature bath at 25°C, sheet-shaped non-aqueous electrolyte secondary batteries were charged at a constant current of 0.05C (the current value for discharging the rated capacity based on the 1-hour rate in 1 hour is set as 1C, and the same applies below) for 10 hours, then discharged at a constant current of 0.2C to 2.5V, and then charged at a constant current-constant voltage to 4.2V, and stored at 60°C for 24 hours.
[0440] Next, it was discharged at a constant current of 0.2C to 2.5V, and then charged at a constant current-constant voltage to 4.2V. The above operation was repeated twice, and it was stored at 60°C for 72 hours.
[0441] Furthermore, the voltage drop was evaluated after being charged to 4.1V at a constant current-constant voltage of 0.2C and stored at 60°C for 72 hours.
[0442] Table 3 shows the voltage drop of the embodiments (relative values with embodiment C-2 set to 100).
[0443]
[0444] According to Table 3, it is clear that the non-aqueous electrolyte (Examples C-3 to C-5) formed by further adding specific compounds to a non-aqueous electrolyte secondary battery having a non-aqueous electrolyte containing hexafluorophosphate, bis(fluorosulfonyl)imide salt and a compound containing anion represented by general formula (1) in a specific amount suppressed the voltage drop associated with self-discharge.
[0445] <Examples D-1~2, Comparative Examples D-1~2>
[0446] [The production of the positive electrode]
[0447] LiNi will be used as the positive electrode active material 0.83 Mn 0.06 Co 0.11O2 (90 parts by weight), acetylene black (7 parts by weight as a conductive material), and polyvinylidene fluoride (PVdF) (3 parts by weight as a binder) were mixed in N-methyl-2-pyrrolidone and slurried. The resulting slurry was uniformly coated onto a 15 μm thick aluminum foil, dried, and then rolled to form the positive electrode. It should be noted that the density of the positive electrode active material layer is 3.0 g / cm³. 3 .
[0448] Manufacturing of non-aqueous electrolyte secondary batteries
[0449] Except for the positive electrode described above, a sheet-shaped non-aqueous electrolyte secondary battery was fabricated following the same steps as in Example B. Using the non-aqueous electrolyte described in Table 4, non-aqueous electrolyte secondary batteries were fabricated as non-aqueous electrolyte secondary batteries for Examples D-1~2 and Comparative Examples D-1~2.
[0450] [Evaluation of Heat Output]
[0451] In a constant temperature bath at 25°C, the sheet-shaped non-aqueous electrolyte secondary battery was charged to 3.7V at a constant current of 0.05C, then charged to 4.3V at a constant current-constant voltage of 0.2C, and then discharged at a constant current of 0.2C to 2.8V.
[0452] Furthermore, after charging to 4.1V at a constant current-constant voltage of 0.2C, the battery was stored at 60°C for 24 hours, followed by constant current discharge down to 2.8V at 0.2C. Then, after charging to 4.3V at a constant current-constant voltage of 0.2C, the negative electrode was removed from the battery and placed in the test cell along with the electrolyte. Measurements were performed using a Calvet calorimeter. The temperature was increased at 1 K / min, and the calorific value was measured from 80°C to 200°C.
[0453] Table 4 shows the heat generation of the embodiments and comparative examples (relative values with comparative example D-1 set to 100). The lower the heat generation, the better the thermal stability of the battery is considered to be.
[0454]
[0455] According to Table 4, it is clear that for non-aqueous electrolyte secondary batteries that contain hexafluorophosphate, bis(fluorosulfonyl)imide salt, and a compound containing an anion represented by general formula (1) in a specific amount (Examples D-1~2), heat generation is suppressed compared to non-aqueous electrolytes (Comparative Examples D-1~2) where the ratio of hexafluorophosphate to bis(fluorosulfonyl)imide salt exceeds a specific ratio.
[0456] <Examples E-1~4, Comparative Examples E-1~4>
[0457] [Preparation of non-aqueous electrolytes]
[0458] Under a dry argon atmosphere, LiPF6 (as a hexafluorophosphate), LiFSI (as a bis(fluorosulfonyl)imide salt), LiCH3OSO3 (as a compound containing an anion represented by general formula (2)), and LiC2H5OSO3 were dissolved in a mixture of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) to achieve the concentrations listed in Table 1, based on the concentrations in the non-aqueous electrolyte. It should be noted that in Tables 5-7, "compound (2)" refers to a compound containing an anion represented by general formula (2).
[0459] [Fabrication of non-aqueous electrochemical battery cells and evaluation of self-discharge]
[0460] Except for the use of the non-aqueous electrolyte described above, sheet-like non-aqueous electrochemical cell cells were fabricated following the same steps as in Example A. Self-discharge was evaluated using the obtained sheet-like non-aqueous electrochemical cell cells following the same steps as in Example A. Table 5 shows the self-discharge of the examples and comparative examples (with comparative example E-1 set as 100 as a relative value).
[0461]
[0462] As can be clearly seen from Table 5, for non-aqueous electrolyte secondary batteries that contain hexafluorophosphate, bis(fluorosulfonyl)imide salt and compounds containing anions represented by general formula (2) in specific amounts (Examples E-1 to 4), self-discharge is suppressed compared to non-aqueous electrolytes that do not contain compounds containing anions represented by general formula (2) (Comparative Examples E-1 to 2) and non-aqueous electrolytes that do not contain hexafluorophosphate (Comparative Examples E-3 to 4).
[0463] <Examples F-1~5>
[0464] [Preparation of non-aqueous electrolytes]
[0465] Under a dry argon atmosphere, LiPF6 as a hexafluorophosphate, LiFSI as a bis(fluorosulfonyl)imide salt, LiCH3OSO3 as a compound containing an anion represented by general formula (2), and other compounds (VC (ethylene carbonate), LiBOB (lithium bis(oxalate)borate), LiPO2F2) listed in Table 6 were dissolved in a mixture of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) in a manner that, based on the concentrations recorded in Table 6, were achieved using a non-aqueous electrolyte concentration meter.
[0466] [Manufacturing of non-aqueous electrolyte secondary batteries and evaluation of voltage drop]
[0467] Except for the use of the non-aqueous electrolyte described above, sheet-like non-aqueous electrochemical cell cells were fabricated following the same steps as in Example C. Using the obtained sheet-like non-aqueous electrochemical cell cells, voltage drop was evaluated following the same steps as in Example C. Table 6 shows the voltage drop self-discharge of the examples (relative to Example F-2 set to 100).
[0468]
[0469] As can be clearly seen from Table 6, the non-aqueous electrolyte (Examples F-3 to F-5) obtained by further adding specific compounds to a non-aqueous electrolyte secondary battery having a non-aqueous electrolyte containing hexafluorophosphate, bis(fluorosulfonyl)imide salt and anion containing the general formula (2) in a specific amount suppressed the voltage drop associated with self-discharge.
[0470] <Examples G-1~2, Comparative Examples G-1~4>
[0471] [Preparation of non-aqueous electrolytes]
[0472] The non-aqueous electrolyte described in Table 7 was prepared following the same steps as in Example F.
[0473] [Manufacturing and heat generation evaluation of non-aqueous electrolyte secondary batteries]
[0474] Except for the use of the non-aqueous electrolyte described above, a sheet-shaped non-aqueous electrolyte secondary battery was manufactured following the same steps as in Example D. The heat generation of the obtained sheet-shaped non-aqueous electrolyte secondary battery was evaluated following the same steps as in Example D. Table 7 shows the heat generation of the examples and comparative examples (relative values with Comparative Example G-1 set to 100).
[0475]
[0476] As can be clearly seen from Table 7, for a non-aqueous electrolyte secondary battery having a specific content of hexafluorophosphate, bis(fluorosulfonyl)imide salt and a compound containing anion represented by general formula (2) (Examples G-1~2), heat generation is suppressed compared to a non-aqueous electrolyte (Comparative Examples G-1~2) that does not contain a compound containing anion represented by general formula (2) and a non-aqueous electrolyte (Comparative Examples G-2~4) in which the ratio of hexafluorophosphate / bis(fluorosulfonyl)imide salt exceeds a specific ratio.
Claims
1. An electrolyte comprising a bis(fluorosulfonyl)imide salt, a hexafluorophosphate, a compound containing an anion represented by the following general formula (1), and a non-aqueous solvent, The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 0.
45. In the electrolyte, the content of a compound containing an anion represented by the general formula (1) is 0.03% by mass or more in 100% by mass. R 1 SO3 - (1) R 1 This represents a halogen atom.
2. An electrolyte comprising a bis(fluorosulfonyl)imide salt, a hexafluorophosphate, a compound containing an anion represented by the following general formula (2), and a non-aqueous solvent. The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 1. In the electrolyte, the content of a compound containing an anion represented by the general formula (2) is 0.01% by mass or more in 100% by mass. R 2 SO3 - (2) R 2 It represents an alkyl group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom.
3. The electrolyte according to claim 1 or 2, wherein, The concentration of the bis(fluorosulfonyl)imide salt in the electrolyte is 8% by mass or more.
4. The electrolyte according to any one of claims 1 to 3, wherein, The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is 0.01 or more.
5. The electrolyte according to any one of claims 1 to 4, wherein, The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 0.
2.
6. The electrolyte according to claim 1, wherein, The mass ratio of the compound containing the anion represented by the general formula (1) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 3.7 or less.
7. The electrolyte according to claim 1 or 6, wherein, The mass ratio of the compound containing the anion represented by the general formula (1) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 0.0001 or more.
8. The electrolyte according to any one of claims 1, 6, and 7, wherein, The bis(fluorosulfonyl)imide salt is LiN(FSO2)2. The hexafluorophosphate is LiPF6. Compounds containing the anion represented by the general formula (1) are compounds represented by the following general formula (1-1). LiR 1 SO3 (1-1) R 1 This represents a halogen atom.
9. The electrolyte according to any one of claims 1, 6, 7, and 8, wherein, The electrolyte further comprises at least one compound (A) selected from the following: cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, cyclic compounds having ether bonds, non-fluorinated carboxylic esters, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, boron-containing anionic compounds, compounds containing oxalate complex anions, and compounds containing phosphate anions having P=O and PF bonds, wherein the bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and compounds containing anions represented by the general formula (1) are excluded.
10. The electrolyte according to claim 9, wherein, The compound (A) comprises at least one compound selected from the compounds containing oxalate complex anions, compounds containing phosphate anions having P=O and PF bonds, cyclic carbonates having carbon-carbon unsaturated bonds, and fluorinated cyclic carbonates.
11. The electrolyte according to claim 2, wherein, The mass ratio of the compound containing the anion represented by the general formula (2) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 3.7 or less.
12. The electrolyte according to claim 2 or 11, wherein, The mass ratio of the compound containing the anion represented by the general formula (2) in the electrolyte to the mass of the bis(fluorosulfonyl)imide salt is 0.0001 or more.
13. The electrolyte according to any one of claims 2, 11, and 12, wherein, The bis(fluorosulfonyl)imide salt is LiN(FSO2)2. The hexafluorophosphate is LiPF6. Compounds containing the anion represented by the general formula (2) are compounds represented by the following general formula (2-1). LiR 2 SO3 (2-1) R 2 It represents an alkyl group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom.
14. The electrolyte according to any one of claims 2, 11, 12, and 13, wherein, The electrolyte further comprises at least one compound (A) selected from the following: cyclic carbonates having carbon-carbon unsaturated bonds, fluorinated cyclic carbonates, organic compounds having isocyanate groups, organic compounds having isocyanuric acid skeletons, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having cyano groups, silicon-containing compounds, aromatic compounds, cyclic compounds having ether bonds, non-fluorinated carboxylic esters, carboxylic anhydrides, compounds containing triple bonds, phosphazene compounds, cyclic acetal compounds, boron-containing anionic compounds, compounds containing oxalate complex anions, and compounds containing phosphate anions having P=O and PF bonds, wherein the bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and compounds containing anions represented by the general formula (2) are excluded.
15. The electrolyte according to claim 14, wherein, The compound (A) comprises at least one compound selected from the compounds containing oxalate complex anions, compounds containing phosphate anions having P=O and PF bonds, cyclic carbonates having carbon-carbon unsaturated bonds, and fluorinated cyclic carbonates.
16. A method for manufacturing an electrolyte, the method comprising: The process of dissolving bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and a compound containing an anion represented by the following general formula (1) in a non-aqueous solvent, The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 0.
45. In 100% by mass of the electrolyte, the content of the compound containing the anion represented by the general formula (1) is 0.03% by mass or more. R 1 SO3 - (1) R 1 This represents a halogen atom.
17. A method for manufacturing an electrolyte, the method comprising: The process of dissolving bis(fluorosulfonyl)imide salt, the hexafluorophosphate, and a compound containing anion represented by the following general formula (2) in a non-aqueous solvent, The mass ratio of the hexafluorophosphate to the bis(fluorosulfonyl)imide salt in the electrolyte is less than 1. In 100% by mass of the electrolyte, the content of the compound containing the anion represented by the general formula (2) is 0.01% by mass or more. R 2 SO3 - (2) R 2 It represents an alkyl group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom, or an alkoxy group having 1 to 3 carbon atoms that are optionally substituted with a halogen atom.
18. A battery comprising a positive electrode, a negative electrode, and an electrolyte according to any one of claims 1 to 15.
19. The battery according to claim 18, wherein, The positive electrode comprises a compound represented by the following formula (3), That 1+x MO2 (3) In the composition formula (3), x satisfies -0.1≤x≤0.5, and M contains an element containing at least one transition metal.
20. The battery according to claim 19, wherein, The Ni content in M is above 55 mol%.
21. The battery according to claim 18, wherein, The positive electrode comprises a compound represented by the following formula (4), LiMn 1-y Feb y PO4 (4) In equation (4), y satisfies 0 <y≤1。 22. A method for manufacturing a battery, the method comprising: The process of housing the positive and negative electrodes in the outer casing, and The process of injecting the electrolyte of any one of claims 1 to 15 into the outer casing.
23. A vehicle comprising the battery according to any one of claims 18 to 21.
Citation Information
Patent Citations
Lithium bis(fluorosulfonyl) imide composition
JP2018035059A
Non-aqueous electrolytic solution and energy device using the same
JP2023130374A
Nonaqueous electrolyte solution, and nonaqueous electrolyte secondary battery
WO2011099585A1